Photosensitive composition, cured film, color filter, light shielding film, optical element, solid-state imaging element, infrared sensor, headlight unit
By using a photosensitive composition containing zirconium nitride-based particles and an appropriate amount of Fe atoms, a cured film with excellent pattern formation and excellent electrode corrosion resistance was prepared, and the problems of deterioration of electrode patterns and insufficient corrosion resistance in the prior art were solved.
Patent Information
- Application Number
- CN202180018752.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-06
- Filing Date
- 2021-02-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-02-17
AI Technical Summary
In the prior art, when using a particle composition containing zirconium, the pattern of the electrode is easily deteriorated or the desired pattern cannot be formed, and the corrosion resistance is insufficient.
A photosensitive composition containing zirconium nitride-based particles, resin, polymerizable compound and photopolymerization initiator was used, and an appropriate amount of Fe atoms was added to the zirconium nitride-based particles, and the content of Fe atoms was controlled to be between 0.001 and 0.400 mass %, so as to improve pattern formation and corrosion resistance of the electrode.
A cured film with excellent pattern formation and excellent electrode corrosion resistance is achieved, which improves the pattern formation effect and reduces the corrosion risk of electrodes.
Smart Images

Figure CN115280238B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a photosensitive composition, a cured film, a color filter, a light-shielding film, an optical element, a solid-state imaging element, an infrared sensor, and a headlight unit. Background Art
[0002] A color filter used in a liquid crystal display device includes a light-shielding film called a black matrix in order to shield light between colored pixels and improve contrast.
[0003] Furthermore, currently, small and thin camera units are mounted on mobile terminals of electronic devices such as mobile phones and PDAs (Personal Digital Assistants). Solid-state image sensors such as CCD (Charge Coupled Device) image sensors and CMOS (Complementary Metal-Oxide Semiconductor) image sensors are provided with light-shielding films in order to prevent noise and improve image quality.
[0004] For example, Patent Document 1 discloses a colored resin composition comprising (A) an alkali-soluble resin, (B) a coloring material, (C) an organic solvent, and (D) a photosensitizer, wherein the colored resin composition contains at least zirconium dioxide compound particles as the coloring material (B), and the crystallite size of zirconium nitride contained in the zirconium dioxide compound particles, as determined from the half-value width of the peak originating from the (111) plane in the X-ray diffraction spectrum when CuKα rays are used as the X-ray source, is 10 nm or more and 60 nm or less (Claim 1, paragraph 0012). This colored resin composition is described as having excellent light-shielding properties in the visible region and excellent black matrix, etc. (paragraphs 0012, 0112, etc.).
[0005] Previous technical literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2019 / 059359 Summary of the invention
[0008] Technical issues to be solved by the invention
[0009] A composition containing particles containing zirconium may be used to form a cured film processed into a pattern on a substrate having an electrode pattern formed thereon.
[0010] Therefore, it is obvious that when the inventors of the present invention coated a composition containing zirconium-containing particles on a substrate having an electrode pattern formed thereon to produce a cured film formed in a pattern, depending on the type of zirconium-containing particles, the electrode pattern may deteriorate (corrode) or the desired pattern may not be obtained (reduction in pattern formability).
[0011] Therefore, the present invention aims to provide a photosensitive composition capable of producing a cured film having excellent pattern forming properties and excellent electrode corrosion resistance. Another object of the present invention is to provide a cured film, a color filter, a light shielding film, an optical element, a solid-state imaging element, an infrared sensor, and a headlight unit using the photosensitive composition.
[0012] Means for solving technical problems
[0013] As a result of intensive studies, the present inventors have found that the above-mentioned problems can be solved by the following structure, and have completed the present invention.
[0014] [1]
[0015] A photosensitive composition comprising:
[0016] Zirconium nitride particles containing one or more selected from zirconium nitride and zirconium oxynitride;
[0017] Resin;
[0018] polymerizable compounds; and
[0019] Photopolymerization initiator,
[0020] The zirconium nitride-based particles contain 0.001 to 0.400 mass % of Fe atoms relative to the total mass of the zirconium nitride-based particles.
[0021] [2]
[0022] The photosensitive composition according to [1], wherein the zirconium nitride-based particles contain 0.010 to 0.150 mass % of the Fe atoms relative to the total mass of the zirconium nitride-based particles.
[0023] 〔3〕
[0024] The photosensitive composition according to [1] or [2], wherein the zirconium nitride-based particles contain Cl atoms.
[0025] [4]
[0026] The photosensitive composition according to [3], wherein the content of the Cl atom is 0.001 to 0.300 mass % based on the total mass of the zirconium nitride-based particles.
[0027] 〔5〕
[0028] The photosensitive composition according to [3] or [4], wherein in the zirconium nitride-based particles, a mass ratio of the content of the Fe atoms to the content of the Cl atoms is 0.008 to 1.5.
[0029] [6]
[0030] The photosensitive composition according to any one of [1] to [5], wherein the zirconium nitride-based particles comprise: a core portion comprising one or more selected from zirconium nitride and zirconium oxynitride; and a metal oxide coating layer that coats the core portion and is formed of a metal oxide.
[0031] 〔7〕
[0032] The photosensitive composition according to [6], wherein the metal oxide contains silicon dioxide or aluminum oxide.
[0033] 〔8〕
[0034] The photosensitive composition according to [6] or [7], wherein the content of the metal oxide coating layer is 3 to 7% by mass based on the total mass of the zirconium nitride-based particles.
[0035] 〔9〕
[0036] The photosensitive composition according to any one of [1] to [8], further comprising a black pigment.
[0037] 〔10〕
[0038] A cured film formed using the photosensitive composition described in any one of [1] to [9].
[0039]
[11]
[0040] A light-shielding film, which is the cured film described in
[10] .
[0041]
[12]
[0042] A color filter comprising the cured film described in
[10] .
[0043] 〔13〕
[0044] An optical element comprising the cured film described in
[10] .
[0045]
[14]
[0046] A solid-state imaging device comprising the cured film described in
[10] .
[0047] 〔15〕
[0048] An infrared sensor comprising the cured film described in
[10] .
[0049]
[16]
[0050] A headlight unit is used for a vehicle, and the headlight unit comprises:
[0051] light source; and
[0052] a light shielding portion that shields at least a portion of the light emitted from the light source,
[0053] The light shielding portion includes the cured film described in
[10] .
[0054] Effects of the Invention
[0055] According to the present invention, a photosensitive composition capable of producing a cured film having excellent pattern forming properties and excellent electrode corrosion resistance can be provided. In addition, the present invention can also provide a cured film, a color filter, a light shielding film, an optical element, a solid-state imaging element, an infrared sensor, and a headlight unit using the above composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 It is a schematic cross-sectional view showing a structural example of a solid-state imaging device.
[0057] Figure 2 It is a magnified representation Figure 1 Schematic cross-sectional view of an imaging unit included in the solid-state imaging device shown.
[0058] Figure 3 It is a schematic cross-sectional view showing a structural example of an infrared sensor.
[0059] Figure 4 It is a schematic diagram showing a structural example of a headlight unit.
[0060] Figure 5 It is a schematic perspective view showing a structural example of a light shielding portion of a headlight unit.
[0061] Figure 6 It is a schematic diagram showing an example of a light distribution pattern by a light shielding portion of a headlight unit.
[0062] Figure 7 It is a schematic diagram showing another example of the light distribution pattern by the light shielding portion of the headlight unit. DETAILED DESCRIPTION
[0063] Hereinafter, the present invention will be described in detail.
[0064] Although the description of the constituent elements described below may be made based on representative embodiments of the present invention, the present invention is not limited to these embodiments.
[0065] In addition, in this specification, the numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0066] Furthermore, in the description of groups (atomic groups) in this specification, the description without mentioning whether they are substituted or unsubstituted includes groups without substituents and groups with substituents. For example, "alkyl" includes not only alkyl groups without substituents (unsubstituted alkyl groups) but also alkyl groups with substituents (substituted alkyl groups).
[0067] In addition, "actinic rays" or "radiation" in this specification refers to, for example, the bright line spectrum of mercury lamps such as g-rays, h-rays, and i-rays, far ultraviolet rays represented by excimer lasers, extreme ultraviolet rays (EUV light), X-rays, electron beams (EB), etc. In addition, in the present invention, light refers to actinic rays or radiation.
[0068] Furthermore, unless otherwise specified, the term "exposure" in this specification includes not only exposure based on mercury lamps, far ultraviolet rays represented by excimer lasers, extreme ultraviolet rays, X-rays, EUV light, etc., but also drawing based on particle beams such as electron beams and ion beams.
[0069] Furthermore, in this specification, "(meth)acrylate" means acrylate and methacrylate. In this specification, "(meth)acrylic acid" means acrylic acid and methacrylic acid. In this specification, "(meth)acryloyl" means acryloyl and methacryloyl. In this specification, "(meth)acrylamide" means acrylamide and methacrylamide. In this specification, "monomer" has the same meaning as "monomer: monomer".
[0070] In this specification, "ppm" means "parts per million (10 -6 ) means one part per million, and "ppb" means "parts per billion (10 -9 ): one billionth, "ppt" means "parts per trillion (10 -12 ): one trillionth."
[0071] In addition, in this specification, the weight average molecular weight (Mw) is a polystyrene conversion value based on the GPC (Gel Permeation Chromatography) method.
[0072] In this specification, the GPC method is based on a method using HLC-8020GPC (manufactured by TOSOH CORPORATION), TSKgel SuperHZM-H, TSKgel SuperHZ4000, TSKgel SuperHZ2000 (manufactured by TOSOH CORPORATION, 4.6 mmID×15 cm) as a column, and THF (tetrahydrofuran) as an eluent.
[0073] Unless otherwise specified, the bonding direction of the divalent group (e.g., -COO-) described in this specification is not limited. For example, when Y in the compound represented by the general formula "XYZ" is -COO-, the above compound can be "XO-CO-Z" or "X-CO-OZ".
[0074] In this specification, a component being black means that the component has absorption in the entire wavelength range of 400 to 700 nm.
[0075] [Photosensitive composition (composition)]
[0076] The photosensitive composition of the present invention (hereinafter also referred to simply as "composition") comprises: zirconium nitride-based particles (hereinafter also referred to simply as "specific particles") comprising one or more selected from zirconium nitride and zirconium oxynitride;
[0077] Resin;
[0078] polymerizable compounds; and
[0079] Photopolymerization initiator,
[0080] The specific particles contain 0.001 to 0.400 mass % of Fe atoms based on the total mass of the specific particles.
[0081] Although the mechanism by which the subject of the present invention is solved by using the composition having the above structure is not clear, the present inventors believe as follows.
[0082] It is believed that by including a predetermined amount or more of Fe atoms in the specific particles, the specific particles and the developer are more likely to interact with each other, and the specific particles are less likely to remain as residues after the pattern formation of the cured film by development treatment, etc. Therefore, it can be inferred that by setting the content of Fe atoms in the specific particles to a predetermined amount or more, the pattern forming property of the cured film is improved.
[0083] On the other hand, it is believed that if the content of Fe atoms contained in the specific particles is too much, the amount of Fe atoms remaining on the electrode and the substrate after development increases, thereby causing corrosion of the electrode. Therefore, it can be inferred that the corrosion resistance of the electrode is excellent by setting the content of Fe atoms in the specific particles to below a specified amount.
[0084] Furthermore, the composition of the present invention is also excellent in spectral characteristics (light-shielding properties), suppression of outgassing including chlorine, viscosity stability over time, and adhesion of a cured film to a substrate.
[0085] Hereinafter, as long as any one of the pattern forming property when forming a cured film, the corrosion resistance of the electrode of the cured film, the spectral characteristics (light shielding property) of the cured film, the inhibitory property of chlorine gas degassing of the cured film, the viscosity stability of the composition over time, and the adhesion of the cured film to the substrate is excellent, the effect of the present invention can be said to be excellent.
[0086] Furthermore, if degassing of chlorine gas is suppressed, contamination of the substrate due to chlorine gas can be suppressed, and contamination of the heating device and / or exposure device due to chlorine gas can be suppressed.
[0087] Hereinafter, the components contained in the composition of the present invention will be described.
[0088] [Zirconium nitride-based particles (specific particles)]
[0089] The composition of the present invention contains specific particles.
[0090] The specific particles contain one or more selected from zirconium nitride and zirconium oxynitride.
[0091] Furthermore, the specific particles contain Fe atoms (iron atoms), and the content of the Fe atoms is 0.001 to 0.400 mass % relative to the total mass of the specific particles.
[0092] The specific particles are preferably used as a black pigment.
[0093] The content of the specific particles is preferably 5 to 90% by mass, more preferably 15 to 80% by mass, and further preferably 35 to 70% by mass, based on the total solid content of the composition.
[0094] Furthermore, as described later, the composition of the present invention may contain a colorant (preferably a black pigment) as described later, and the total content of the specific particles and the colorant (preferably a black pigment) is preferably 5 to 90% by mass, more preferably 35 to 80% by mass, and further preferably 50 to 70% by mass relative to the total solid content of the composition.
[0095] In the composition, the content of the specific particles is preferably 30 to 100% by mass, more preferably 40 to 95% by mass, and further preferably 55 to 85% by mass, based on the total content of the specific particles and the colorant (preferably a black pigment).
[0096] In this specification, the "solid content" of the composition refers to the components that form the cured film (light-shielding film). When the composition contains a solvent (organic solvent, water, etc.), it refers to all components other than the solvent. In addition, as long as it is a component that forms a cured film (light-shielding film), a liquid component can also be regarded as a solid component.
[0097] The average primary particle size of the specific particles is not particularly limited, but is preferably 5 to 100 nm, more preferably 5 to 50 nm, and even more preferably 5 to 30 nm from the viewpoint of achieving a better balance between handleability and temporal stability of the composition.
[0098] In the present invention, the average primary particle size of the particles can be measured using a transmission electron microscope (TEM). As a transmission electron microscope, for example, a transmission electron microscope HT7700 manufactured by Hitachi High-Technologies Corporation can be used.
[0099] The maximum length of the particle image obtained using a transmission electron microscope (Dmax: the maximum length of two points on the contour of the particle image) and the maximum length perpendicular to the maximum length (DV-max: when the image is sandwiched between two straight lines parallel to the maximum length, the shortest length connecting the two straight lines perpendicularly) were measured, and the average value (Dmax×DV-max) was multiplied. 1 / 2 The particle diameters of 100 particles were measured by this method, and the arithmetic mean value was taken as the average primary particle diameter of the particles.
[0100] When producing specific particles, a gas phase reaction method is generally used, and specifically, an electric furnace method and a thermal plasma method can be mentioned. Among these production methods, the thermal plasma method is preferred because of the fact that there is less mixing of impurities, the particle size is easily uniform, and the productivity is high.
[0101] Examples of a method for generating thermal plasma include direct current arc discharge, multiphase arc discharge, high frequency (RF) plasma, and mixed plasma. High frequency plasma with little mixing of impurities originating from electrodes is preferred.
[0102] As a specific method for producing specific particles based on the thermal plasma method, for example, a method of synthesizing specific particles by evaporating a powder material containing zirconium (powder containing zirconium) by high-frequency thermal plasma, introducing nitrogen as a carrier gas into the device, and nitriding the powder containing zirconium during the cooling process can be cited. When the powder containing zirconium is evaporated by high-frequency thermal plasma, components containing Fe atoms and the like can be evaporated together as needed. In addition, the thermal plasma method is not limited to the above.
[0103] In addition, the specific particles obtained as above are usually formed only by a core portion, and the core portion contains one or more selected from zirconium nitride and zirconium oxynitride. A coating layer as described later can be formed on the surface of the core portion to serve as a specific particle containing a core portion and a coating layer covering the core portion.
[0104] As a more specific method for producing specific particles, reference can be made to the method described in paragraphs 0037 to 0089 of International Publication No. 2010 / 147098. For example, instead of the Ag powder of International Publication No. 2010 / 147098, a component containing Fe atoms described later is used, and the component is mixed with a powder material containing zirconium (zirconium-containing powder) as a raw material to produce specific particles contained in the composition of the present invention.
[0105] The zirconium-containing powder used for the production of specific particles is preferably of high purity. The zirconium-containing powder may be a zirconium monomer, or a zirconium compound as required. From the viewpoint of facilitating the introduction of Cl atoms, as described later, into the specific particles finally obtained, zirconium chloride is also preferably used as the zirconium compound.
[0106] Furthermore, the zirconium-containing powder may contain Fe atoms, and these Fe atoms may serve as all or part of the supply source of Fe atoms contained in the specific particles.
[0107] The zirconium-containing powder may be used alone or in combination of two or more.
[0108] The method for adding Fe atoms to the zirconium-containing powder is not particularly limited, and examples thereof include a method of introducing Fe atoms at the stage of obtaining the zirconium-containing powder. More specifically, when producing the zirconium-containing powder, a material containing Fe atoms such as stainless steel (SUS) is used as a reaction vessel, or a material containing Fe atoms is used as a punch and a pulverizer when crushing the zirconium-containing powder, so that Fe atoms can be attached to the surface of the zirconium-containing powder.
[0109] Furthermore, as described above, when the thermal plasma method is used in the production of specific particles, in addition to the zirconium-containing powder as a raw material, a component containing Fe atoms (Fe powder, etc.) is added and nitrided by the thermal plasma method, so that Fe atoms can also be contained in the specific particles.
[0110] In addition, the Fe atoms contained in the specific particles may be contained in any form of, for example, ions, metal compounds (including complexes), intermetallic compounds, alloys, oxides, composite oxides, nitrides, oxynitrides, sulfides, and oxysulfides. Furthermore, the Fe atoms contained in the specific particles may exist as impurities at positions between crystal lattices, or may exist as impurities in an amorphous state at grain boundaries.
[0111] Furthermore, the Fe atoms contained in the specific particles may be present in the core portion, may be present in the coating layer described later, or may be present in other forms.
[0112] The specific particles preferably further contain Cl atoms (chlorine atoms).
[0113] The method for containing Cl atoms in the specific particles is not particularly limited, and an example thereof includes a method of using a zirconium-containing powder containing Cl atoms such as zirconium chloride partially or entirely as the zirconium-containing powder used for producing the specific particles.
[0114] In addition, the Cl atoms contained in the specific particles may be contained in any form, for example, ions and metal compounds (including complexes), etc. Furthermore, the Cl atoms contained in the specific particles may exist as impurities at positions between crystal lattices, or may exist as impurities in an amorphous state at grain boundaries.
[0115] Furthermore, the Cl atoms contained in the specific particles may be present in the core portion, may be present in the cladding layer described later, or may be present in other forms.
[0116] The specific particles preferably include a core portion, and the core portion includes one or more selected from zirconium nitride and zirconium oxynitride. In addition, the specific particles may be formed only of the core portion, or may include a coating layer described later.
[0117] The content of the core portion is preferably 60 to 100% by mass, more preferably 85 to 100% by mass, and even more preferably more than 93% by mass and less than 97% by mass, based on the total mass of the specific particles.
[0118] The total content of zirconium nitride and zirconium oxynitride is preferably 90 to 100% by mass, more preferably 95 to 99.999% by mass, and further preferably 99 to 99.99% by mass, based on the total mass of the core portion.
[0119] The total content of zirconium nitride and zirconium oxynitride is preferably 60 to 100 mass %, more preferably 85 to 100 mass %, and further preferably more than 93 mass % and less than 97 mass % based on the total mass of the specific particles.
[0120] From the viewpoint of better pattern formation of the cured film and / or corrosion resistance of the electrode, the content of Fe atoms in the cured film is 0.001 to 0.400 mass %, preferably 0.010 to 0.250 mass %, and more preferably 0.010 to 0.150 mass % relative to the total mass of the specific particles. In addition, when the specific particles contain the coating layer described later, the coating layer portion is also included in the specific particles. That is, in the case of the total mass of the specific particles, when the specific particles contain the coating layer, the total mass of the specific particles refers to the mass of the specific particles also including the coating layer portion.
[0121] The content of Fe atoms is preferably 0.001 to 0.400 mass %, more preferably 0.010 to 0.250 mass %, and further preferably 0.010 to 0.150 mass %, based on the total mass of the core portion.
[0122] As described above, the specific particles preferably contain Cl atoms. It is considered that when the specific particles contain Cl atoms, they appropriately interact with the developer, thereby improving pattern forming properties.
[0123] From the viewpoint of being able to reduce the Cl atom content in the outgassing of the cured film and / or from the viewpoint of better pattern forming properties, the Cl atom content is preferably 0.001 to 0.500 mass %, more preferably 0.001 to 0.300 mass %, further preferably 0.010 to 0.300 mass %, and particularly preferably 0.020 to 0.200 mass % relative to the total mass of the specific particles or the core.
[0124] The mass ratio of the content of Fe atoms to the content of Cl atoms in the specific particles or the core (content of Fe atoms / content of Cl atoms) is preferably 0.001 to 400, more preferably 0.008 to 2.5, further preferably 0.008 to 1.5, and particularly preferably 0.008 to 1.0.
[0125] It is believed that if the mass ratio is below a predetermined value, corrosion of the electrode caused by the presence of a large number of Fe atoms can be suppressed. It is believed that if the mass ratio is above a predetermined value, corrosion of the electrode caused by Cl atoms can be suppressed by Fe atoms.
[0126] The content of Zr atoms (zirconium atoms) is preferably 20 to 70% by mass, more preferably 30 to 60% by mass, and further preferably 40 to 50% by mass, based on the total mass of the specific particles or the core.
[0127] The content of N atoms (nitrogen atoms) is preferably 10 to 40% by mass, more preferably 20 to 40% by mass, and further preferably 28 to 38% by mass, based on the total mass of the specific particles or the core.
[0128] The content of O atoms (oxygen atoms) is preferably 0 to 35% by mass, more preferably 5 to 28% by mass, and further preferably 13 to 23% by mass, based on the total mass of the specific particles or the core.
[0129] In addition, the content of Zr atoms, Fe chlorine and Cl atoms in specific particles is measured by ICP emission spectrometry. ICP emission spectrometry is a method of applying plasma energy to a sample to excite elements (atoms) in the sample, measuring the light released when the excited elements (atoms) return to a low energy level, and determining the type of the element (atom) from the wavelength of the light. Regarding ICP emission spectrometry, an ICP emission spectrometry device "ICPE-9800" (product name) manufactured by Shimadzu Corporation can be used.
[0130] Furthermore, the contents of N atoms and O atoms in specific particles can be measured by the inert gas fusion thermal conductivity method. For the inert gas fusion thermal conductivity method, an oxygen / nitrogen analyzer "EMGA-620W / C" (product name) manufactured by HORIBA, Ltd. can be used.
[0131] <Coating layer>
[0132] The specific particles may include a core portion including one or more selected from zirconium nitride and zirconium oxynitride; and a coating layer coating the core portion.
[0133] Hereinafter, specific particles including a coating layer may also be referred to as coated particles.
[0134] The cladding layer is a layer that covers the core portion.
[0135] The coating with the coating layer may cover the entire surface of the core or only a part thereof. That is, as long as the coating layer is disposed on a part of the surface of the core, a part of the core may be exposed on the surface.
[0136] The presence or absence of coating can be determined using, for example, FE-STEM / EDS (field emission scanning transmission electron microscope equipped with energy dispersive X-ray analyzer).
[0137] The coating layer may be an organic substance, an inorganic substance, or a mixture of an organic substance and an inorganic substance.
[0138] Examples of the organic coating layer include a coating layer obtained by surface-treating a core portion with an epoxy resin and a silane compound containing an amino group.
[0139] Among them, the coating layer is preferably a metal oxide coating layer formed of a metal oxide.
[0140] The metal in the metal oxide constituting the metal oxide coating layer is not limited, and may be a typical element metal or a transition metal. Furthermore, the metal may be a semimetal such as silicon.
[0141] Examples of the above-mentioned metals include Al (aluminum), Si (silicon), Zn (zinc), germanium (Ge), hafnium (Hf), gallium (Ga), molybdenum (Mo), titanium (Ti), zirconium (Zr), vanadium (V), tantalum (Ta), niobium (Nb), cobalt (Co), chromium (Cr), copper (Cu), manganese (Mn), ruthenium (Ru), iron (Fe), nickel (Ni), tin (Sn) and silver (Ag).
[0142] Among them, the above-mentioned metal is preferably Al (aluminum) or Si (silicon).
[0143] The metal oxide may be an oxide of a single metal (for example, the metals described above) or a composite oxide of a plurality of metals.
[0144] The above-mentioned metal oxides include aluminum oxide (Al2O3), silicon dioxide (SiO2), ZnO, GeO2, TiO2, ZrO2, HfO2, Sn2O3, Mn2O3, Ga2O3, M02O3, Ta2O5, V2O5 and Nb2O s wait.
[0145] Among them, the metal oxide preferably contains aluminum oxide or silicon dioxide.
[0146] The above-mentioned metal oxide can be used alone or in combination. Wherein, when using two or more metal oxides, the content of the metal oxide with the highest content is preferably 50% by mass or more, more preferably 80% by mass or more relative to the total mass of the two or more metal oxides. The upper limit is less than 100% by mass.
[0147] The metal oxide coating layer being formed of a metal oxide means that the metal oxide coating layer is substantially formed of only a metal oxide.
[0148] The above-mentioned metal oxide coating layer is essentially formed only by metal oxide. For example, in the metal oxide coating layer, the content of metal oxide (preferably one or two of aluminum oxide and silicon dioxide) is 90 to 100 mass % (preferably 95 to 100 mass %, more preferably 99 to 100 mass %) relative to the total mass of the metal oxide coating layer.
[0149] Furthermore, the content of the metal oxide coating layer is preferably 0.1 to 15% by mass, more preferably 1 to 10% by mass, and even more preferably 3 to 7% by mass, based on the total mass of the coated particles.
[0150] The content of the metal oxide coating layer can be determined using ESCA (Electron Spectroscopy for Chemical Analysis).
[0151] There is no particular limitation on the method for producing coated particles. For example, a method for producing a powder matrix of black titanium oxynitride coated with a silicon dioxide film, i.e., black titanium oxynitride powder, described in paragraphs 0018 to 0019 and 0025 of Japanese Patent Gazette No. 2015-117302, can be cited, in which the powder matrix of black titanium oxynitride is replaced with specific particles formed only by a core portion.
[0152] Another example of a method for producing coated particles is a method in which, in the inorganic treatment step in the surface treatment of titanium dioxide described in paragraph 0059 of JP-A-2017-014522, titanium dioxide is replaced with specific particles consisting only of a core portion.
[0153] Another example of a method for producing coated particles is a method described in Japanese Patent Application Laid-Open No. 08-059240 (Japanese Patent No. 3314542) in which a gas barrier thin film is formed on the surface of specific particles consisting only of the core instead of particles of lower titanium oxide.
[0154] 〔Colorant〕
[0155] The composition of the present invention may further contain a colorant.
[0156] In addition, the coloring agent is a component different from the specific particles.
[0157] Examples of the colorant include pigments and dyes.
[0158] The above-mentioned pigment may be an organic pigment or an inorganic pigment.
[0159] The content of the colorant is preferably 1 to 60% by mass, more preferably 5 to 40% by mass, and even more preferably 10 to 25% by mass, based on the total solid content of the composition.
[0160] A part or all of the colorant is preferably a black colorant (black colorant).
[0161] In addition, a plurality of colorants that cannot be used as a black colorant alone may be combined and adjusted so that the entire color becomes black to be used as a black colorant.
[0162] Examples of the black colorant include black pigments and black dyes.
[0163] <Black Pigment>
[0164] The composition of the present invention also preferably contains a black pigment.
[0165] The zirconium nitride-based particles are not included in the black pigment.
[0166] As the black pigment, various known black pigments can be used. The black pigment may be an inorganic pigment or an organic pigment.
[0167] The black color material is preferably an inorganic pigment from the viewpoint of obtaining a cured film with better light resistance.
[0168] The black pigment is preferably a pigment that exhibits black color alone, and more preferably a pigment that exhibits black color alone and absorbs infrared rays.
[0169] Among them, the black pigment that absorbs infrared rays has absorption in the infrared region (preferably a wavelength of 650 to 1300 nm), and a black pigment having a maximum absorption wavelength in the wavelength region of 675 to 900 nm is also preferred.
[0170] The particle size of the black pigment is not particularly limited, but is preferably 5 to 100 nm, more preferably 5 to 50 nm, and even more preferably 5 to 30 nm, from the viewpoint of achieving a better balance between handleability and temporal stability of the composition (no sedimentation of the black pigment).
[0171] (Inorganic Pigments)
[0172] The inorganic pigment is not particularly limited as long as it is a particle having light-shielding properties and containing an inorganic compound, and a known inorganic pigment can be used.
[0173] From the viewpoint of achieving a more excellent low reflectivity and light shielding property of the light shielding film, an inorganic pigment is preferred as the black colorant.
[0174] Examples of inorganic pigments include metal oxides, metal nitrides, and metal oxynitrides containing metal elements of Group 4 such as titanium (Ti) and zirconium (Zr), metal elements of Group 5 such as vanadium (V) and niobium (Nb), and one or more metal elements selected from the group consisting of cobalt (Co), chromium (Cr), copper (Cu), manganese (Mn), ruthenium (Ru), iron (Fe), nickel (Ni), tin (Sn), and silver (Ag).
[0175] As the metal oxide, metal nitride, and metal oxynitride, particles containing other atoms may be used. For example, metal nitride particles containing atoms selected from elements of Groups 13 to 17 of the periodic table (preferably oxygen atoms and / or sulfur atoms) may be used.
[0176] As the manufacturing method of the above-mentioned metal nitride, metal oxide or metal oxynitride, there is no particular limitation as long as a black pigment having the desired physical properties can be obtained, and a known manufacturing method such as a gas phase reaction method can be used. As the gas phase reaction method, an electric furnace method and a thermal plasma method can be cited, but from the viewpoint of less mixing of impurities, easy uniformity of particle size, and high productivity, a thermal plasma method is preferred.
[0177] The surface of the metal nitride, metal oxide or metal oxynitride may be coated. The coating may be applied to the entire particle surface or a portion thereof. The coating is preferably applied with a silane coupling agent, silicon dioxide or aluminum oxide.
[0178] Among them, from the viewpoint of being able to suppress the occurrence of undercut when forming a light-shielding film, a nitride or oxynitride of one or more metals selected from titanium, vanadium, zirconium and niobium is more preferred. And, from the viewpoint that the moisture resistance of the light-shielding film is more excellent, an oxynitride of one or more metals selected from titanium, vanadium, zirconium and niobium is further preferred, and titanium nitride, titanium oxynitride (titanium black), zirconium nitride, and zirconium oxynitride are particularly preferred. The above-mentioned nitride or oxynitride of one or more metals selected from titanium, vanadium, zirconium and niobium may further contain an element selected from Na, Mg, K, Ka, Rb, Cs, Hf, Ta, Cr, Mo, W, Mn, Ru, Os, Co, Ni, Pd, Pt, Cu, Ag, Au, Zn, In, Cl, Br, and I. The content of the above-mentioned elements is preferably 0.001 to 5% by mass relative to the total mass of the nitride or oxynitride of the metal.
[0179] Regarding titanium black, for example, titanium black described in paragraphs 0122 to 0129 of International Publication No. 2018 / 139186 can be used. The preferred range is also the same.
[0180] Carbon black can also be mentioned as the inorganic pigment.
[0181] Examples of carbon black include furnace black, channel black, thermal black, acetylene black, and lamp black.
[0182] As carbon black, carbon black produced by a known method such as an oil furnace method may be used, or a commercially available product may be used. Specific examples of commercially available carbon black products include organic pigments such as CI Pigment Black 1 and inorganic pigments such as CI Pigment Black 7.
[0183] As carbon black, surface-treated carbon black is preferred. The surface state of carbon black particles can be modified by surface treatment, and the dispersion stability in the composition can be improved. As surface treatment, coating treatment based on resin, surface treatment introducing acidic groups and surface treatment based on silane coupling agent can be cited.
[0184] As carbon black, resin-coated carbon black is preferred. By coating the surface of carbon black particles with insulating resin, the light-shielding property and insulation property of the light-shielding film can be improved. In addition, the reliability of the image display device can be improved by reducing leakage current, etc. Therefore, the light-shielding film is preferably used for applications requiring insulation, etc.
[0185] Examples of the coating resin include epoxy resins, polyamides, polyamideimides, novolac resins, phenol resins, urea resins, melamine resins, polyurethanes, diallyl phthalate resins, alkylbenzene resins, polystyrene, polycarbonates, polybutylene terephthalate, and modified polyphenylene ethers.
[0186] From the viewpoint of further improving the light-shielding property and insulating property of the light-shielding film, the content of the coating resin is preferably 0.1 to 40% by mass, more preferably 0.5 to 30% by mass, based on the total amount of the carbon black and the coating resin.
[0187] (Organic Pigments)
[0188] The organic pigment is not particularly limited as long as it has light-shielding properties and contains particles of an organic compound, and a known organic pigment can be used.
[0189] In the present invention, examples of the organic pigment include bisbenzofuranone compounds, methine azo compounds, perylene compounds, and azo compounds, and bisbenzofuranone compounds or perylene compounds are preferred.
[0190] Examples of the bisbenzofuranone compound include compounds described in JP-A-2010-534726, JP-A-2012-515233, and JP-A-2012-51534. The bisbenzofuranone compound can be obtained as "Irgaphor B1ack" (product name) manufactured by BASF.
[0191] Examples of the perylene compound include compounds described in JP-A-62-1753 and JP-B-63-26784. The perylene compound can be obtained as CI Pigment Black 21, 30, 31, 32, 33, and 34.
[0192] <Black Dye>
[0193] As the black dye, a dye that exhibits black alone can be used, for example, pyrazole azo compounds, pyrromethene compounds, aniline azo compounds, triphenylmethane compounds, anthraquinone compounds, benzylidene compounds, oxonol compounds, pyrazolotriazole azo compounds, pyridone azo compounds, cyanine compounds, phenothiazine compounds and pyrrolopyrazole azoimine compounds can be used.
[0194] Furthermore, as black dyes, reference can be made to compounds described in Japanese Patent Application Publication No. 64-90403, Japanese Patent Application Publication No. 64-91102, Japanese Patent Application Publication No. 1-94301, Japanese Patent Application Publication No. 6-11614, Japanese Patent No. 2592207, U.S. Patent No. 4808501, U.S. Patent No. 5667920, U.S. Patent No. 505950, U.S. Patent No. 5667920, Japanese Patent Application Publication No. 5-333207, Japanese Patent Application Publication No. 6-35183, Japanese Patent Application Publication No. 6-51115 and Japanese Patent Application Publication No. 6-194828, and the like, and these contents are incorporated into this specification.
[0195] Specific examples of these black dyes include dyes specified in the color index (CI) of Solvent Black 27 to 47, and dyes specified in the CI of Solvent Black 27, 29, or 34 are preferred.
[0196] In addition, commercially available products of these black dyes include Spilon Black MH, Black BH (above, manufactured by Hodogaya Chemical Co., Ltd.), VALIFAST Black 3804, 3810, 3820, 3830 (above, manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD.), Savinyl Black RLSN (above, manufactured by Clariant Chemicals), KAYASET Black KR, K-BL (above, manufactured by Nippon Kayaku CO., LTD.) and the like.
[0197] Furthermore, as black dye, pigment polymer can also be used. As pigment polymer, compounds described in Japanese Patent Publication No. 2011-213925 and Japanese Patent Publication No. 2013-041097 can be cited. Furthermore, polymerizable dyes having polymerizability in the molecule can also be used, and as commercially available products, for example, RDW series manufactured by Wako Pure Chemical Industries, LTD. can be cited.
[0198] Furthermore, as described above, a plurality of dyes having colors other than black may be combined to be used as black dyes. As such coloring dyes, for example, in addition to color dyes (color dyes) such as R (red), G (green), and B (blue), dyes described in paragraphs 0027 to 0200 of Japanese Patent Application Laid-Open No. 2014-42375 may be used.
[0199] 〔Resin〕
[0200] The composition of the present invention contains a resin.
[0201] In addition, the molecular weight of the resin exceeds 3000. When the molecular weight distribution of the resin is polydisperse, the weight average molecular weight exceeds 3000.
[0202] The content of the resin in the composition is preferably 3 to 60% by mass, more preferably 7 to 40% by mass, and further preferably 15 to 35% by mass, based on the total solid content of the composition.
[0203] When two or more resins are used simultaneously, the total content is preferably within the above range.
[0204] The resin also preferably contains an acid group (eg, a carboxyl group, a sulfonic acid group, a monosulfate group, -OPO(OH)2, a monophosphate group, a boric acid group and / or a phenolic hydroxyl group).
[0205] The resin also preferably contains a curable group. Examples of the curable group include ethylenically unsaturated groups (such as (meth)acryloyl groups, vinyl groups, and styryl groups) and cyclic ether groups (such as epoxy groups and oxetanyl groups).
[0206] The resin of the present invention may be any of a dispersant and an alkali-soluble resin.
[0207] <Dispersant>
[0208] The dispersant is, for example, a resin capable of suppressing aggregation and / or sedimentation of components such as pigments present in the composition in a solid state.
[0209] The content of the dispersant is preferably 3 to 60% by mass, more preferably 7 to 40% by mass, and further preferably 13 to 25% by mass, based on the total solid content of the composition.
[0210] The dispersant preferably contains an acid group.
[0211] The dispersant also preferably contains a curable group.
[0212] Examples of the dispersant include a resin containing a structural unit having a graft chain and / or a resin containing a radial structure.
[0213] The structural unit having a graft chain in the resin containing a structural unit having a graft chain may be a structural unit represented by any one of the following formulae (1) to (4).
[0214] [Chemical formula 1]
[0215]
[0216] [Chemical formula 2]
[0217]
[0218] In formula (1) to formula (4), Q 1 is a group represented by any one of Formula (QX1), Formula (QNA) and Formula (QNB), Q 2 is a group represented by any one of Formula (QX2), Formula (QNA) and Formula (QNB), Q 3 is a group represented by any one of Formula (QX3), Formula (QNA) and Formula (QNB), Q 4 It is a group represented by any one of Formula (QX4), Formula (QNA) and Formula (QNB).
[0219] In formula (QX1) to formula (QX4), formula (QNA), and formula (QNB), *a represents a bonding position on the main chain side, and *b represents a bonding position on the side chain side.
[0220] In formulas (1) to (4), W 1 , W 2 , W 3 and W 4 Each independently represents a single bond, an oxygen atom or NH.
[0221] In formulas (1) to (4) and (QX1) to (QX4), X 1 , X 2 , X 3 , X 4 and X 5 Each independently represents a hydrogen atom or a monovalent organic group. From the viewpoint of synthetic limitations, it is preferred that X 1 , X 2 , X 3 , X 4 and X 5 Each of them is independently a hydrogen atom or an alkyl group having 1 to 12 carbon atoms, more preferably each of them is independently a hydrogen atom or a methyl group, and even more preferably a methyl group.
[0222] In formula (1) to formula (4), Y 1 , Y 2 , Y 3 and Y 4 Each of Y and Y independently represents a single bond or a divalent linking group, and the structure of the linking group is not particularly limited. 1 , Y 2 , Y 3 and Y 4 Specific examples of the divalent linking group include the following linking groups (Y-1) to (Y-23).
[0223] In the following linking groups, A represents the same as W in formula (1) to formula (4). 1 ~W 4 B represents the bonding position of any one of A. 1 ~W 4 The bonding position of the group on the opposite side of any one.
[0224] [Chemical formula 3]
[0225]
[0226] In formulas (1) to (4), Z 1 , Z 2 , Z 3 and Z 4 Each independently represents a monovalent substituent. The structure of the substituent is not particularly limited, and specific examples thereof include alkyl, hydroxy, alkoxy, aryloxy, heteroaryloxy, alkylthio, arylthio, heteroarylthio, and amino groups.
[0227] Among them, Z is particularly preferred from the viewpoint of improving dispersibility. 1 , Z 2 , Z 3 and Z 4 The substituent represented is preferably a group having a steric repulsive effect, more preferably each independently being an alkyl group or an alkoxy group having 5 to 24 carbon atoms, and particularly preferably each independently being a branched alkyl group having 5 to 24 carbon atoms, a cyclic alkyl group having 5 to 24 carbon atoms, or an alkoxy group having 5 to 24 carbon atoms. In addition, the alkyl group included in the alkoxy group may be any of a linear, branched, and cyclic type.
[0228] And, Z 1 , Z 2 , Z 3 and Z 4 The substituent represented by is also preferably a group containing a curable group such as a (meth)acryloyl group. Examples of the group containing the above-mentioned curable group include "-O-alkylene-(-O-alkylene-) AL -(meth)acryloyloxy". AL represents an integer of 0 to 5, preferably 1. The above-mentioned alkylene groups preferably each independently have 1 to 10 carbon atoms. When the above-mentioned alkylene groups have a substituent, the substituent is preferably a hydroxyl group.
[0229] The above-mentioned substituent may be a group containing an onium structure.
[0230] The group containing an onium structure is a group having an anion part and a cation part. Examples of the anion part include an oxygen anion (-O - ) partial structure. Among them, it is preferred that in the repeating units represented by formula (1) to formula (4), the oxygen anion (-O- ) is directly bonded to the end of the repeating structure with n, m, p or q, and more preferably, in the repeating unit represented by formula (1), is directly bonded to the end of the repeating structure with n (i.e., -(-OC j H 2j -CO-) n -right end) directly bonded.
[0231] Examples of the cation of the cation portion of the group containing an onium structure include ammonium cations. In the case where the cation portion is an ammonium cation, the cation portion is a cation containing a cationic nitrogen atom (>N + <) partial structure. Cationic nitrogen atom (>N + <) is preferably bonded to 4 substituents (preferably organic groups), and 1 to 4 of them are preferably alkyl groups having 1 to 15 carbon atoms. In addition, it is also preferred that at least one (preferably one) of the 4 substituents is a group containing a curable group. Examples of the group containing the curable group that can be the above-mentioned substituent include the above-mentioned "-O-alkylene-(-O-alkylene-) AL -(meth)acryloyloxy".
[0232] In formulae (1) to (4), n, m, p and q are each independently an integer of 1 to 500, more preferably an integer of 2 to 500, and even more preferably an integer of 6 to 500.
[0233] In formula (3), R 3 The term "alkylene group" refers to a branched or linear alkylene group, preferably an alkylene group having 1 to 10 carbon atoms, and more preferably an alkylene group having 2 or 3 carbon atoms.
[0234] In formula (4), R 4 represents a hydrogen atom or a monovalent organic group, and the monovalent structure is not particularly limited. 4 Preferably, it is a hydrogen atom, an alkyl group, an aryl group or a heteroaryl group, and more preferably a hydrogen atom or an alkyl group. 4 In the case of an alkyl group, the alkyl group is preferably a linear alkyl group having 1 to 20 carbon atoms, a branched alkyl group having 3 to 20 carbon atoms, or a cyclic alkyl group having 5 to 20 carbon atoms.
[0235] In the resin containing a structural unit having a graft chain, the total content of the structural unit represented by any one of formulae (1) to (4) is preferably 2 to 100% by mass, more preferably 6 to 100% by mass, based on the total mass of the resin.
[0236] The resin containing a radial structure is, for example, a compound represented by the following general formula (X-2).
[0237] (A 2 -R 4 -S-) n R 3(-SR 5 -P 2 ) m (X-2)
[0238] In the above general formula (X-2), A 2 represents a monovalent organic group containing at least one site selected from an organic pigment structure, a heterocyclic structure, an acid group, a group having a basic nitrogen atom, a urea group, a carbamate group, a group having a coordinating oxygen atom, a hydrocarbon group having 4 or more carbon atoms, an alkoxysilyl group, an epoxy group, an isocyanate group, and a hydroxyl group. n A 1 It can be the same or different.
[0239] In the above general formula (X-2), R 4 , R 5 Each independently represents a single bond or a divalent organic linking group.
[0240] Examples of the divalent organic linking group include groups containing 1 to 100 carbon atoms, 0 to 10 nitrogen atoms, 0 to 50 oxygen atoms, 1 to 200 hydrogen atoms, and 0 to 20 sulfur atoms. The divalent organic linking group is preferably an alkylene group which may contain a substituent. The carbon number of the alkylene group is preferably 2 to 5. The substituent that the alkylene group may contain is preferably an acid group.
[0241] n R 4 can be the same or different. 5 It can be the same or different.
[0242] In the above general formula (X-2), R 3 It represents an organic linking group with a valence of (m+n). m+n is preferably 3-10.
[0243] As R 3 Examples of the (m+n)-valent organic linking group include groups containing 1 to 60 carbon atoms, 0 to 10 nitrogen atoms, 0 to 50 oxygen atoms, 1 to 100 hydrogen atoms, and 0 to 20 sulfur atoms.
[0244] In the above general formula (X-2), m represents an integer of 1-8.
[0245] Furthermore, in the above general formula (X-2), n represents an integer of 2 to 9.
[0246] Furthermore, P in the general formula (X-2) 2 represents a polymer skeleton and can be selected from known polymers according to the purpose. 2The polymer skeleton is preferably formed by at least one of a polymer or copolymer selected from vinyl monomers, ester polymers, ether polymers, carbamate polymers, amide polymers, epoxy polymers, polysiloxane polymers, and modified products or copolymers thereof [e.g., copolymers containing polyether / polycarbamate copolymers, polyether / vinyl monomer polymers, etc. (which may also be any of random copolymers, block copolymers, and graft copolymers.)].
[0247] Among them, the polymer skeleton is preferably a polymer skeleton formed of a polymer or copolymer of a vinyl monomer, and more preferably a polymer skeleton formed of a polymer or copolymer of (meth)acrylic acid and / or (meth)acrylic acid esters.
[0248] As the dispersant, for example, the polymer compounds described in paragraphs 0071 to 0141 of International Publication No. 2019 / 069690 can also be used.
[0249] <Alkali-soluble resin>
[0250] The alkali-soluble resin is, for example, a resin that is soluble in an alkaline solution such as an alkaline aqueous solution.
[0251] The alkali-soluble resin is preferably a resin different from the above-mentioned dispersant.
[0252] The content of the alkali-soluble resin is preferably 0.1 to 30% by mass, more preferably 0.5 to 25% by mass, and further preferably 1 to 10% by mass, based on the total solid content of the composition.
[0253] The alkali-soluble resin preferably contains an acid group as an alkali-soluble group for achieving alkali solubility.
[0254] The alkali-soluble resin also preferably contains a curable group. The alkali-soluble resin also preferably contains a structural unit having a curable group. The content of the structural unit containing the curable group is preferably 5 to 60 mol%, more preferably 10 to 45 mol%, and further preferably 15 to 35 mol% relative to the total structural units of the alkali-soluble resin.
[0255] Alkali-soluble resins such as [benzyl (meth)acrylate / (meth)acrylic acid / other addition-polymerizable vinyl monomers as required] copolymers and [allyl (meth)acrylate / (meth)acrylic acid / other addition-polymerizable vinyl monomers as required] copolymers are preferred because they have an excellent balance among film strength, sensitivity, and developability.
[0256] The other addition polymerizable vinyl monomers may be used alone or in combination of two or more.
[0257] From the viewpoint of obtaining a more excellent moisture resistance of the light-shielding film, the copolymer preferably has a curable group, and more preferably contains an ethylenically unsaturated group such as a (meth)acryloyl group.
[0258] For example, as the above-mentioned other addition polymerizable vinyl monomers, a monomer having a curable group can be used, so that the curable group is introduced into the copolymer. In addition, a curable group (preferably an ethylenically unsaturated group such as a (meth)acryloyl group) can be introduced into part or all of one or more of the units derived from (meth)acrylic acid in the copolymer and / or the units derived from the above-mentioned other addition polymerizable vinyl monomers.
[0259] As the alkali-soluble resin, for example, the resin described in paragraphs 0143 to 0163 of International Publication No. 2019 / 069690 can be used.
[0260] The weight average molecular weight of the resin such as the dispersant and the alkali-soluble resin is preferably independently more than 3,000 and 100,000 or less, and more preferably more than 3,000 and 50,000 or less.
[0261] The acid value of the resin such as the dispersant and the alkali-soluble resin is preferably independently 10 to 300 mgKOH / g, more preferably 30 to 200 mgKOH / g.
[0262] The amine value of the resin such as the dispersant and the alkali-soluble resin is preferably independently 0 to 100 mgKOH / g, more preferably 0 to 25 mgKOH / g.
[0263] 〔Polymerizable compounds〕
[0264] The composition of the present invention contains a polymerizable compound.
[0265] In the present specification, the polymerizable compound is a compound that polymerizes under the action of a photopolymerization initiator described later, and is a component different from a resin such as a dispersant and an alkali-soluble resin.
[0266] The polymerizable compound is preferably a low molecular weight compound. The low molecular weight compound referred to here is preferably a compound having a molecular weight of 3,000 or less.
[0267] The content of the polymerizable compound in the composition is not particularly limited, but is preferably 1 to 35% by mass, more preferably 4 to 25% by mass, and further preferably 8 to 20% by mass relative to the total solid content of the composition. The polymerizable compound may be used alone or in combination of two or more. When two or more polymerizable compounds are used, the total content is preferably within the above range.
[0268] The polymerizable compound is preferably a compound containing an ethylenically unsaturated group.
[0269] That is, the composition of the present invention preferably contains a low molecular weight compound containing an ethylenically unsaturated group as a polymerizable compound.
[0270] The polymerizable compound preferably contains one or more ethylenically unsaturated bonds such as (meth)acryloyl groups, more preferably two or more, further preferably three or more, and particularly preferably five or more. The upper limit is, for example, 15 or less.
[0271] The polymerizable compound is preferably a compound represented by the following formula (Z-6).
[0272] [Chemical formula 4]
[0273]
[0274] In formula (Z-6), E each independently represents -(CH2) y -CH2-O-, -(CH2) y -CH(CH3)-O-, -(CH2) y -CH2-CO-O-, -(CH2) y -CH(CH3)-CO-O-, -CO-(CH2) y -CH2-O-, -CO-(CH2) y -CH(CH3)-O-, -CO-(CH2) y -CH2-CO-O- or -CO-(CH2) y -CH(CH3)-CO-O-. The right-side bonding position of these groups is preferably the bonding position on the X side.
[0275] y each independently represents an integer of 1-10.
[0276] X's each independently represent a (meth)acryloyl group or a hydrogen atom.
[0277] p each independently represents an integer of 0 to 10.
[0278] q represents an integer from 0 to 3.
[0279] In formula (Z-6), the total number of (meth)acryloyl groups is preferably (3+2q) or (4+2q).
[0280] p is preferably an integer of 0-6, more preferably an integer of 0-4.
[0281] The total of each p is preferably 0 to (40+20q), more preferably 0 to (16+8q), and further preferably 0 to (12+6q).
[0282] The compound represented by formula (Z-6) may be used alone or in combination of two or more.
[0283] As the polymerizable compound, for example, compounds described in paragraph 0050 of JP-A-2008-260927, paragraph 0040 of JP-A-2015-068893, paragraph 0227 of JP-A-2013-029760, and paragraphs 0254 to 0257 of JP-A-2008-292970 can also be used.
[0284] 〔Photopolymerization initiator〕
[0285] The above composition contains a photopolymerization initiator.
[0286] As the photopolymerization initiator, there is no particular limitation as long as it can initiate polymerization of the polymerizable compound, and a known photopolymerization initiator can be used. As the photopolymerization initiator, a photopolymerization initiator having photosensitivity in the ultraviolet region to the visible light region is preferred. The photopolymerization initiator may be a photoradical polymerization initiator, or an initiator that generates active free radicals by reacting with a photoexcited sensitizer, or an initiator that initiates cationic polymerization according to the type of the polymerizable compound.
[0287] Furthermore, the photopolymerization initiator preferably has a wavelength of at least 50 (l·mol) in the range of 300 to 800 nm (more preferably 330 to 500 nm). -1 cm -1 ) of the compound having a molar absorption coefficient of .
[0288] The content of the photopolymerization initiator in the composition is preferably 0.5 to 20% by mass, more preferably 1.0 to 10% by mass, and further preferably 1.5 to 8% by mass, based on the total solid content of the composition.
[0289] The photopolymerization initiator may be used alone or in combination of two or more. When two or more polymerization initiators are used in combination, the total content is preferably within the above range.
[0290] As for the photopolymerization initiator, for example, there can be mentioned halogenated hydrocarbon derivatives (for example, compounds containing a triazine skeleton, compounds containing an oxadiazole skeleton, etc.), acylphosphine compounds such as acylphosphine oxide, hexaarylbiimidazole, oxime compounds such as oxime derivatives, organic peroxides, thio compounds, ketone compounds, aromatic onium salts, aminoacetophenone compounds and hydroxyacetophenone, etc.
[0291] Among them, the photopolymerization initiator is preferably an oxime compound, that is, an oxime-based photopolymerization initiator.
[0292] As the photopolymerization initiator, the photopolymerization initiator described in paragraphs 0164 to 0186 of International Publication No. 2019 / 069609 can also be used. In addition, the peroxycinnamate derivative described in Japanese Patent Application Laid-Open No. 2019-167313 can also be used.
[0293] 〔Inhibitor〕
[0294] The composition may contain a polymerization inhibitor.
[0295] As the polymerization inhibitor, for example, a known polymerization inhibitor can be used. As the polymerization inhibitor, for example, phenol-based polymerization inhibitors (for example, p-methoxyphenol, 2,5-di-tert-butyl-4-methylphenol, 2,6-di-tert-butyl-4-methylphenol, 4,4'-thiobis(3-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 4-methoxynaphthol, etc.); hydroquinone-based polymerization inhibitors (for example, hydroquinone, 2,6- di-tert-butylhydroquinone, etc.); quinone-based inhibitors (e.g., benzoquinone, etc.); free radical-based inhibitors (e.g., 2,2,6,6-tetramethylpiperidinium 1-oxyl radical, 4-hydroxy-2,2,6,6-tetramethylpiperidinium 1-oxyl radical, etc.); nitrobenzene-based inhibitors (e.g., nitrobenzene, 4-nitrotoluene, etc.); and phenothiazine-based inhibitors (e.g., phenothiazine, 2-methoxyphenothiazine, etc.); etc.
[0296] Among them, phenol-based polymerization inhibitors and radical-based polymerization inhibitors are preferred because the composition has a more excellent effect.
[0297] The polymerization inhibitor is particularly effective when used together with a resin containing a curable group.
[0298] The content of the polymerization inhibitor in the composition is preferably 0.0001 to 0.5 mass %, more preferably 0.001 to 0.2 mass %, and further preferably 0.008 to 0.05 mass % relative to the total solid content of the composition. The polymerization inhibitor may be used alone or in combination of two or more. When two or more polymerization inhibitors are used in combination, the total content is preferably within the above range.
[0299] The ratio of the content of the polymerization inhibitor to the content of the polymerizable compound in the composition (content of the polymerization inhibitor / content of the polymerizable compound (mass ratio)) is preferably 0.00005 to 0.02, and more preferably 0.0001 to 0.005.
[0300] 〔Surfactant〕
[0301] The composition may contain a surfactant, which helps improve the coating properties of the composition.
[0302] When the composition contains a surfactant, the content of the surfactant is preferably 0.001 to 2.0% by mass, more preferably 0.003 to 0.5% by mass, and further preferably 0.005 to 0.1% by mass based on the total solid content of the composition.
[0303] The surfactant may be used alone or in combination of two or more. When two or more surfactants are used in combination, the total amount is preferably within the above range.
[0304] Examples of the surfactant include fluorine-based surfactants, nonionic surfactants, cationic surfactants, anionic surfactants, and silicone-based surfactants.
[0305] Examples of the fluorine-based surfactant include MEGAFACE F171, MEGAFACE F172, MEGAFACE F173, MEGAFACE F176, MEGAFACE F177, MEGAFACE F141, MEGAFACE F142, MEGAFACE F143, MEGAFACE F144, MEGAFACE R30, MEGAFACE F437, MEGAFACE F475, MEGAFACE F479, MEGAFACE F482, MEGAFACE F554, MEGAFACE F780, and MEGAFACE F781F (all manufactured by DIC CORPORATION); Fluorad FC430, Fluorad FC431, and Fluorad FC171 (all manufactured by Sumitomo 3M Limited); Surflon S-382, Surflon SC-101, Surflon SC-103, Surflon SC-104, Surflon SC-105, Surflon SC-1068, Surflon SC-381, Surflon SC-383, Surflon S-393 and Surflon KH-40 (all manufactured by Asahi Glass Co., LTD.); and PF636, PF656, PF6320, PF6520 and PF7002 (manufactured by OMNOVA Solutions Inc.), etc.
[0306] As the fluorine-based surfactant, a block polymer can also be used, and specific examples thereof include compounds described in Japanese Unexamined Patent Application Publication No. 2011-89090.
[0307] 〔Solvent〕
[0308] The composition preferably contains a solvent.
[0309] As the solvent, for example, a known solvent can be used.
[0310] The content of the solvent in the composition is preferably 10 to 90% by mass, more preferably 10 to 45% by mass, and still more preferably 20 to 40% by mass, in terms of solid content concentration of the composition.
[0311] The solvent may be used alone or in combination of two or more. When two or more solvents are used in combination, the total solid content of the composition is preferably adjusted to be within the above range.
[0312] Examples of the solvent include water and organic solvents.
[0313] <Organic Solvents>
[0314] Examples of the organic solvent include acetone, methyl ethyl ketone, cyclohexane, ethyl acetate, ethylene dichloride, tetrahydrofuran, toluene, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, acetylacetone, cyclohexanone, cyclopentanone, diacetone alcohol, ethylene glycol monomethyl ether acetate, ethylene glycol ethyl ether acetate, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether acetate, 3-methoxypropanol, methoxyethoxyethanol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, 3-methoxypropyl acetate, N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, butyl acetate, methyl lactate, N-methyl-2-pyrrolidone, and ethyl lactate, but are not limited thereto.
[0315] 〔Silica-based particles〕
[0316] The composition may contain silica-based particles (particles containing silicon dioxide as a main component).
[0317] From the viewpoint of further improving the effects of the present invention, the content of the silica-based particles is preferably 0.1 to 70% by mass, more preferably 0.2 to 65% by mass, and further preferably 0.3 to 60% by mass based on the total solid content of the composition.
[0318] In addition, the silica particles are a material different from the above-mentioned black pigment. That is, the silica particles are not included in the black pigment even if they are black.
[0319] It is considered that, when the composition contains silica particles, the silica particles tend to be localized on the surface of a cured film (light-shielding film) formed using the composition, and appropriate concavities and convexities can be formed on the surface of the cured film (light-shielding film), thereby suppressing the reflectivity of the cured film (light-shielding film).
[0320] Furthermore, the silica-based particles may be silica particles themselves (silica particles), or may be modified silica particles including silica particles and a coating layer coating the surface of the silica particles.
[0321] From the viewpoint of excellent balance between low reflectivity and light shielding of the obtained cured film (especially light shielding film), the average primary particle size of the silica particles is preferably 1 to 250 nm, more preferably 5 to 200 nm, and further preferably 10 to 150 nm. Furthermore, as long as the average primary particle size of the silica particles is within the above range, low reflectivity is more excellent.
[0322] The average primary particle size of the silica-based particles can be measured by the same method as that for the average primary particle size of the specific particles.
[0323] The refractive index of the silica-based particles is not particularly limited, but is preferably 1.10 to 1.60, more preferably 1.15 to 1.55, from the viewpoint of achieving more excellent low reflectivity of the cured film.
[0324] Furthermore, the silica particles in the silica-based particles may be hollow particles or solid particles.
[0325] Hollow particles refer to particles with a cavity inside the particle. Hollow particles can be particles with a cavity inside and a shell surrounding the cavity. In addition, hollow particles can also be particles with a plurality of cavities inside.
[0326] Solid particles refer to particles that do not substantially have a cavity inside the particles.
[0327] It is considered that the hollow particles have cavities inside and have a smaller specific gravity than particles without a hollow structure, and therefore the hollow particles float to the surface of the coating film formed using the composition, further enhancing the effect localized on the surface of the cured film.
[0328] Moreover, the refractive index of the hollow particles themselves is lower than that of particles without a hollow structure. For example, when the hollow particles are composed of silica, the hollow silica particles have air with a low refractive index (refractive index = 1.0), so the refractive index of the particles themselves becomes 1.2 to 1.4, which is significantly lower than that of ordinary silica (refractive index = 1.6). Therefore, it is considered that by forming a cured film using a composition containing hollow particles, the hollow particles with a low refractive index are concentrated on the surface of the cured film, and an AR (Anti-Reflection) type low reflection effect can be obtained, thereby improving the low reflectivity of the cured film.
[0329] Examples of the hollow particles include hollow silica particles described in Japanese Unexamined Patent Application Publication No. 2001-233611 and Japanese Patent No. 3272111.
[0330] As the hollow particles, for example, THRULYA4110 (product name, manufactured by JGC Catalysts and Chemicals Ltd.) can also be used.
[0331] As solid particles, IPA-ST, IPA-ST-L, IPA-ST-ZL, MIBK-ST, MIBK-ST-L, CHO-ST-M, PGM-AC-2140Y, PGM-AC-4130Y (all of which are product names manufactured by Nissan Chemical Corporation) and the like are preferably used.
[0332] As the silica particles, a plurality of silica particles may be linked together in a chain, that is, bead-like silica particles. The bead-like silica particles are preferably a plurality of spherical colloidal silica particles having a particle size of 5 to 50 nm connected by silica containing a metal oxide.
[0333] Examples of the bead-like colloidal silica particles include silica sols described in Japanese Patent No. 4328935 and Japanese Patent Application Laid-Open No. 2013-253145.
[0334] The modified silica particles are obtained by reacting unmodified silica particles with a compound having an alkoxysilyl group, or preferably, modified silica particles obtained by reacting a modified silica particle precursor described below with a compound B described below.
[0335] The modified silica particle precursor is a particle obtained by surface-treating unmodified silica particles (silica particles that have not been surface-treated with compound A) with compound A. When the silica particles in the modified silica particles are solid particles, the modified silica particle precursor is also a solid particle, and when the silica particles in the modified silica particles are hollow particles, the modified silica particle precursor is also a hollow particle.
[0336] Compound A is a compound represented by the following formula A. Compound A is used as a so-called silane coupling agent.
[0337] Formula A Si(R A ) 4-n (X A ) n
[0338] R A It represents a monovalent organic group containing a reactive group.
[0339] Examples of the monovalent organic group containing a reactive group include an alkyl group substituted with a reactive group and an aryl group substituted with a reactive group.
[0340] The carbon number of the alkyl group is preferably 1 to 30, more preferably 2 to 20, and further preferably 2 to 10. The alkyl group may be linear, branched, or cyclic. In addition, the methylene group in the alkyl group may be substituted with -0- or -NHC(O)-.
[0341] The carbon number of the aryl group is preferably 6 to 30, more preferably 6 to 20, and even more preferably 6 to 15. The aryl group may be a monocyclic ring or may have a condensed ring structure of two or more rings.
[0342] When a substituent (reactive group) is present, the number of carbon atoms in the alkyl group and the aryl group does not include the number of carbon atoms in the substituent.
[0343] Examples of the reactive group include an ethylenically unsaturated group, a thiol group, an epoxy group, an amino group, and an ethynyl group. From the viewpoint of achieving more excellent effects of the present invention, an ethylenically unsaturated group, a thiol group, an epoxy group, or an amino group is preferred.
[0344] Examples of the ethylenically unsaturated group include a (meth)acryloyl group and a vinyl group.
[0345] X A represents a hydroxyl group or a monovalent hydrolyzable group, and a monovalent hydrolyzable group is preferred.
[0346] As the hydrolyzable group, an alkoxy group, an allyloxy group and a halogen atom can be mentioned. From the viewpoint of the better effect of the present invention, an alkoxy group and a halogen atom are preferred, and an alkoxy group is more preferred. As the alkoxy group, an alkoxy group having 1 to 4 carbon atoms is preferred, and an alkoxy group having 1 to 2 carbon atoms is more preferred. As the allyloxy group, an allyloxy group having 6 to 10 carbon atoms is preferred. As the halogen atom, a chlorine atom is preferred.
[0347] n represents an integer of 1 to 3, and is preferably 2 or 3 from the viewpoint of further improving the effect of the present invention. When n is 2 or less, a plurality of R A may be the same or different from each other. When n is 2 or more, multiple X A They may be the same as or different from each other.
[0348] The surface of silica particles (unmodified silica particles) is treated with Compound A to obtain a modified silica particle precursor.
[0349] There is no particular limitation on the method of surface treatment, and examples include a method of contacting compound A with unmodified silica particles in the presence of water. At this time, a layer (hereinafter also referred to as "coating layer A") obtained by a dehydration condensation reaction of a hydroxyl group of XA derived from compound A and a hydroxyl group of silica constituting the unmodified silica particles is formed on the surface of the modified silica particle precursor, and the coating layer A has RA derived from compound A. In other words, it can be said that the modified silica particle precursor has particles containing silica (silicon dioxide particles) and a coating layer A formed on the surface of the particles containing silica. The proportion of the surface treatment of the unmodified silica surface by compound A in the modified silica particle precursor is preferably 10% or more of the unmodified silica surface, more preferably 25% or more, and further preferably 50% or more.
[0350] The modified silica particles are obtained by reacting the reactive group of the modified silica particle precursor with the functional group in the compound B having a functional group and an organic group that react with the reactive group to form a bond. The reaction rate between the reactive group of the modified silica particle precursor and the compound B is preferably 30% or more, more preferably 40% or more, and further preferably 50% or more.
[0351] Examples of the functional group of compound B include an amino group, a hydroxyl group, a carboxyl group, a chlorine atom, a chlorocarbonyl group, an epoxy group, an isocyanate group, a (meth)acryloyl group, a sulfonic acid group, a vinyl group, an azido group (-N3), and a thiol group. Among them, an amino group, a carboxyl group, an epoxy group, a (meth)acryloyl group, or a thiol group is preferred from the viewpoint of excellent reactivity with the reactive group of the modified silica particle precursor.
[0352] Examples of the organic group include monovalent organic groups, and an alkyl group or an aryl group is preferred. The alkyl group and the aryl group may be substituted with a substituent.
[0353] The carbon number of the alkyl group is preferably 1 to 30, more preferably 1 to 25. The alkyl group may have any structure of a linear, branched or cyclic structure.
[0354] The carbon number of the aryl group is preferably 6 to 30, more preferably 6 to 20, and even more preferably 6 to 15. The aryl group may be a monocyclic ring or may have a condensed ring structure of two or more rings.
[0355] When the above alkyl or aryl group is substituted, examples of the substituent include a fluorine atom, -Si(-O-Si(R S )3) m (R S ) 3-m (Multiple R S Each independently represents an alkyl group having 1 to 5 carbon atoms, and m represents an integer of 0 to 3. ), polysiloxane structure, poly(meth)acrylate structure, polyolefin structure, polyether structure, etc. The alkyl group or aryl group as an organic group may be substituted by only one of these substituents, or by two or more of them. In addition, the methylene group in the alkyl group may be substituted by -O- or -NHC(O)-.
[0356] One preferred embodiment of the organic group of compound B is an embodiment in which the organic group includes at least one structure selected from a polyester structure, a poly(meth)acrylate structure, a polyolefin structure, and a polyether structure. Therefore, low reflectivity is further improved.
[0357] One preferred embodiment of the organic group of compound B includes a fluorine atom in the organic group. The content of fluorine atoms in the organic group is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 15% by mass or more.
[0358] One of the preferred forms of the organic group of compound B is a form in which the organic group contains silicon atoms. The content of silicon atoms in the organic group is preferably 10% by mass or more, more preferably 20% by mass or more, and further preferably 30% by mass or more. Specific examples of forms in which the organic group contains silicon atoms include the above-mentioned -Si(-O-Si(R S )3) m (R S ) 3-m The embodiment of the group represented by and the embodiment having the above-mentioned polysiloxane structure.
[0359] Only one of these preferred aspects may be satisfied, or two or more thereof may be satisfied from the viewpoint of low reflectivity.
[0360] The compound B is preferably a compound represented by the following formula B from the viewpoint of having more excellent low reflectivity.
[0361] Type BX B -YB
[0362] X B The monovalent organic group is the same as the above-mentioned organic group, and the preferred embodiment is also the same.
[0363] Y B Specific examples of the functional group are the same as those of the above-mentioned functional group, and preferred embodiments are also the same.
[0364] The compound represented by Formula B may be a compound having a molecular weight of 800 or less, or may be a compound represented by Formula B-1 below. From the viewpoint of achieving more excellent effects of the present invention, the compound represented by Formula B-1 below is preferred.
[0365] Formula B-1 P B -LY B
[0366] P B represents a polymer chain. A polymer chain is a group derived from a polymer and contains a predetermined repeating unit. The polymer chain is preferably capable of bonding to the above-mentioned L in its main chain portion.
[0367] The polymer chain can be selected from known polymers according to the purpose, and examples thereof include polysiloxane, poly(meth)acrylate, polyolefin, polyether, and copolymers thereof.
[0368] L represents a single bond or a divalent linking group. As the divalent linking group, for example, a divalent hydrocarbon group (which may be a divalent saturated hydrocarbon group or a divalent aromatic hydrocarbon group. As the divalent saturated hydrocarbon group, any one of a linear, branched, and cyclic group may be mentioned, preferably with a carbon number of 1 to 20, for example, an alkylene group may be mentioned. And, as the divalent aromatic hydrocarbon group, preferably with a carbon number of 5 to 20, for example, a phenylene group may be mentioned. In addition, it may be an alkenylene group or an alkynylene group.), a divalent heterocyclic group, -O-, -S-, -SO2-, -NR L -、-CO-、-COO-、-CONR L -, -SO3-, -SO2NR L - or a combination of two or more of these groups. (For example, alkyleneoxy, alkyleneoxycarbonyl, alkylenecarbonyloxy, etc.) L represents a hydrogen atom or an alkyl group (preferably having 1 to 10 carbon atoms).
[0369] Y B represents a functional group, which is the same as the functional group in formula B.
[0370] The modified silica particles are obtained by reacting the reactive group of the modified silica particle precursor with the functional group of the compound B. Therefore, a layer (hereinafter also referred to as "coating layer B") containing a reaction product of the reactive group of the modified silica particle precursor and the functional group of the compound B is formed on the surface of the modified silica particles. In other words, it can be said that the modified silica particles have silica particles (particles containing silica) and a coating layer B formed on the surface of the silica particles. The ratio of the particle surface of the modified silica particles that is coated is preferably 10% or more of the particle surface, more preferably 25% or more, and further preferably 50% or more.
[0371] The coating layer of the modified silica particles preferably has a fluorine atom or a silicon atom, and more preferably has a fluorine atom, a polysiloxane structure or a trimethylsilyl group.
[0372] 〔Ultraviolet light absorber〕
[0373] The composition of the present invention may contain an ultraviolet absorber.
[0374] When the composition contains an ultraviolet absorber, the content thereof is preferably 0.01 to 10% by mass, more preferably 0.1 to 8% by mass, and more preferably 1 to 6% by mass based on the total solid content of the composition.
[0375] Examples of the ultraviolet absorber include conjugated diene compounds, and may be a compound represented by the following formula (I).
[0376] [Chemical formula 5]
[0377]
[0378] In formula (I), R 1 and R 2 Each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms, and R 1 and R 2 They may be the same as or different from each other, but they do not both represent hydrogen atoms.
[0379] In formula (I), R 3 and R 4 Each independently represents an electron withdrawing group. The above electron withdrawing group is the Hammett substituent constant σ p An electron withdrawing group having a value of 0.20 or more and 1.0 or less.
[0380] R of the ultraviolet absorber represented by formula (I) 1 ~R 4For the description of the invention, reference can be made to paragraphs 0024 to 0033 of International Publication No. 2009 / 123109 (paragraphs 0040 to 0059 of the corresponding U.S. Patent Application Publication No. 2011 / 0039195), which are incorporated herein. For the compound represented by formula (I), reference can be made to the description of exemplified compounds (1) to (14) of paragraphs 0034 to 0037 of International Publication No. 2009 / 123109 (paragraph 0060 of the corresponding U.S. Patent Application Publication No. 2011 / 0039195), which are incorporated herein.
[0381] 〔Other optional ingredients〕
[0382] The composition may also contain any other components other than the above components. For example, particle components other than the above components, silane coupling agents, sensitizers, co-sensitizers, crosslinking agents, curing accelerators, thermosetting accelerators, plasticizers, diluents and lipid-sensitizing agents may be cited. Furthermore, the composition may contain known additives such as adhesion promoters and other auxiliary agents (for example, conductive particles, fillers, defoamers, flame retardants, leveling agents, peeling accelerators, antioxidants, fragrances, surface tension adjusters and chain transfer agents) on the substrate surface as needed, or may not contain them.
[0383] For example, these components can be referred to in paragraphs 0183 to 0228 of Japanese Patent Application Publication No. 2012-003225 (paragraphs 0237 to 0309 of the corresponding specification of U.S. Patent Application Publication No. 2013 / 0034812), paragraphs 0101 to 0102, 0103 to 0104, and 0107 to 0109 of Japanese Patent Application Publication No. 2008-250074, and paragraphs 0159 to 0184 of Japanese Patent Application Publication No. 2013-195480, and the like, and these contents are incorporated into the specification of the present application.
[0384] [Method for producing the composition]
[0385] Regarding the composition, a dispersion in which a particulate component such as specific particles and / or a black pigment is dispersed is prepared, and the obtained dispersion is preferably further mixed with other components to prepare a composition.
[0386] The dispersion is preferably prepared by mixing the particulate component, the resin and the solvent. Furthermore, it is also preferred that the dispersion contain a polymerization inhibitor.
[0387] The dispersion can be prepared by mixing the above-mentioned components by a known mixing method (for example, a mixing method using a stirrer, a homogenizer, a high-pressure emulsifier, a wet pulverizer, a wet disperser, or the like).
[0388] When preparing the composition, each component may be blended at once, or each component may be dissolved or dispersed in a solvent and then blended sequentially. Furthermore, the order of adding and the operating conditions during blending are not particularly limited.
[0389] In order to remove foreign matter and reduce defects, it is preferred to utilize a filter to filter the composition. As a filter, for example, as long as it is a filter that has always been used for filtering purposes, it can be used without particular restrictions. For example, filters based on fluororesins such as PTFE (polytetrafluoroethylene), polyurethane resins such as nylon, and polyolefin resins such as polyethylene and polypropylene (PP) (including high density, ultra-high molecular weight) can be cited. Among these raw materials, polypropylene (including high-density polypropylene) and preferably nylon.
[0390] The pore size of the filter is preferably 0.1 to 7.0 μm, more preferably 0.2 to 2.5 μm, further preferably 0.2 to 1.5 μm, and particularly preferably 0.3 to 0.7 μm. Within this range, clogging of the filtration of the pigment (including the black pigment) can be suppressed, and fine foreign matter such as impurities and aggregates contained in the pigment can be reliably removed.
[0391] When using filters, different filters can be combined. In this case, filtration through the first filter can be performed only once or twice or more. When combining different filters to perform filtration more than twice, it is preferred that the pore size after the second filtration is the same as or larger than the pore size of the first filtration. In addition, first filters with different pore sizes can be combined within the above range. The pore size here can refer to the nominal value of the filter manufacturer. As commercially available filters, for example, it can be selected from various filters provided by NIHON PALL LTD., Toyo Roshi Kaisha, LTD., Nihon Entegris KK (formerly Mykrolis Corporation) and KITZ MICROFILTER CORPORATION.
[0392] The second filter may be made of the same material as the first filter. The pore size of the second filter is preferably 0.2 to 10.0 μm, more preferably 0.2 to 7.0 μm, and even more preferably 0.3 to 6.0 μm.
[0393] The composition preferably does not contain impurities such as metals, halogen-containing metal salts, acids, and bases. The content of impurities contained in these materials is preferably 1 mass ppm or less, more preferably 1 mass ppb or less, further preferably 100 mass ppt or less, particularly preferably 10 mass ppt or less, and most preferably substantially free (below the detection limit of the measuring device).
[0394] The above impurities can be measured using an inductively coupled plasma mass spectrometer (manufactured by Yokogawa Electric Corporation, Agilent 7500cs model).
[0395] [Manufacturing of Cured Film]
[0396] By curing the composition layer formed using the composition of the present invention, a cured film (including a patterned cured film) can be obtained.
[0397] The method for producing the cured film is not particularly limited, but preferably includes the following steps.
[0398] Composition layer forming step
[0399] Exposure steps
[0400] Development step
[0401] Each step is described below.
[0402] [Composition layer forming step]
[0403] In the composition layer forming step, a composition is applied to a support body or the like before exposure to form a layer of the composition (composition layer). As a support body, for example, a substrate (for example, a substrate containing Si atoms such as a silicon substrate or a glass substrate) or a solid-state imaging element substrate on which an imaging element (light-receiving element) such as a CCD or CMOS is arranged can be used. In addition, as required, a primer layer for improving the close contact with the upper layer, preventing the diffusion of substances and flattening the surface of the substrate can be provided on the support body.
[0404] As the method for applying the composition on the support, various coating methods such as slit coating, inkjet, spin coating, cast coating, roll coating and screen printing can be applied. The film thickness of the composition layer is preferably 0.1 to 10 μm, more preferably 0.2 to 5 μm, and further preferably 0.2 to 3 μm. The drying (prebaking) of the composition layer applied on the support can be performed, for example, at a temperature of 50 to 140° C. for 10 to 300 seconds using a hot plate, an oven, etc.
[0405] [Exposure Step]
[0406] In the exposure step, the composition layer (dried film) formed in the composition layer forming step is exposed by irradiating actinic rays or radiation, and the light-irradiated composition layer is cured.
[0407] As a method of light irradiation, it is preferable to perform light irradiation through a photomask having patterned openings.
[0408] The exposure is preferably performed by irradiation with radiation. The radiation that can be used for exposure is preferably ultraviolet rays such as g-rays, h-rays or i-rays, and the light source is preferably a high-pressure mercury lamp. The irradiation intensity is preferably 5 to 1500 mJ / cm 2 , more preferably 10 to 1000 mJ / cm 2 .
[0409] When the composition contains a thermal polymerization initiator, the composition layer may be heated in the exposure step. The heating temperature is not particularly limited, but is preferably 80 to 250° C. The heating time is preferably 30 to 300 seconds.
[0410] In addition, when the composition layer is heated in the exposure step, the post-heating step described below may also be used. In other words, when the composition layer is heated in the exposure step, the method for producing a cured film may not include the post-heating step.
[0411] [Development Step]
[0412] The development step is a step of developing the composition layer after exposure to form a cured film. The development step dissolves the composition layer in the portion not irradiated with light in the exposure step, leaving only the photocured portion to obtain a patterned cured film.
[0413] The type of developer used in the development step is not particularly limited, but an alkaline developer that does not damage the imaging element and circuit of the substrate is preferred.
[0414] The development temperature is, for example, 20 to 30°C.
[0415] The developing time is, for example, 20 to 90 seconds. In order to more effectively remove the residue, in recent years, 120 to 180 seconds is sometimes implemented. Furthermore, in order to further improve the removability of the residue, the developer is sometimes repeatedly removed every 60 seconds and the developer is re-supplied.
[0416] The alkali developer is preferably an alkaline aqueous solution prepared by dissolving an alkaline compound in water to a concentration of 0.001 to 10% by mass (preferably 0.01 to 5% by mass).
[0417] As for the basic compound, for example, sodium hydroxide, potassium hydroxide, sodium carbonate, sodium silicate, sodium metasilicate, ammonia water, ethylamine, diethylamine, dimethylethanolamine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, choline, pyrrole, piperidine and 1,8-diazabicyclo〔5.4.0〕-7-undecene, etc. (among which, organic bases are preferred).
[0418] When used as an alkali developer, a washing treatment with water is usually performed after development.
[0419] 〔Post-baking〕
[0420] After the exposure step, a heat treatment (post-baking) is preferably performed. Post-baking is a heat treatment after development for complete curing. The heating temperature is preferably 240°C or less, more preferably 220°C or less. The lower limit is not particularly limited, but if efficient and effective processing is considered, it is preferably 50°C or more, more preferably 100°C or more.
[0421] Post-baking can be performed continuously or batchwise using a heating mechanism such as a hot plate, a flow oven (hot air circulation dryer) or a high-frequency heater.
[0422] The above-mentioned post-baking is preferably carried out in an atmosphere with a low oxygen concentration. The oxygen concentration is preferably 19 volume % or less, more preferably 15 volume % or less, further preferably 10 volume % or less, particularly preferably 7 volume % or less, and most preferably 3 volume % or less. The lower limit is not particularly limited, but is actually 10 volume ppm or more.
[0423] Furthermore, the above-mentioned heating may be followed by baking, and curing may be completed by UV (ultraviolet) irradiation.
[0424] At this time, the above-mentioned composition preferably also contains a UV curing agent. The UV curing agent is preferably a UV curing agent that can be cured at the exposure wavelength of the polymerization initiator added for the lithography step based on the usual i-ray exposure, that is, a wavelength shorter than 365nm. As a UV curing agent, for example, Omnirad 2959 manufactured by IGM Resins BV can be cited (corresponding to IRGACURE2959 (former product name, formerly manufactured by BASF)). In the case of UV irradiation, it is preferred that the composition layer is a material that cures at a wavelength of less than 340nm. The lower limit of the wavelength is not particularly limited, and is usually above 220nm. In addition, the exposure amount of UV irradiation is preferably 100 to 5000mJ, more preferably 300 to 4000mJ, and further preferably 800 to 3500mJ. In order to perform low-temperature curing more effectively, the UV curing step is preferably performed after the exposure step. The exposure light source preferably uses an ozone-free mercury lamp.
[0425] [Physical properties of cured film and uses of cured film]
[0426] [Physical properties of cured film]
[0427] The cured film formed using the composition of the present invention can be preferably used as a light-shielding film.
[0428] From the viewpoint of having excellent light-shielding properties, the optical density (OD: Optical Density) of the cured film per 1.5 μm film thickness in the wavelength range of 400 to 1200 nm is preferably greater than 2.0, more preferably greater than 2.5, further preferably greater than 3.0, and particularly preferably greater than 3.5. The upper limit is not particularly limited, but is preferably 10 or less.
[0429] In this specification, the optical density per 1.5 μm film thickness in the wavelength region of 400 to 1200 nm exceeds 2.0, which means that the optical density per 1.5 μm film thickness exceeds 2.0 or more in the entire wavelength region of 400 to 1200 nm.
[0430] Furthermore, the cured film (light-shielding film) preferably has good light-shielding properties for infrared light, and for example, the optical density per 1.5 μm film thickness in light of a wavelength of 940 nm is preferably greater than 2.0, more preferably greater than 3.0. In addition, the upper limit is not particularly limited, but is preferably generally less than 10.
[0431] Moreover, when the cured film is used as a light attenuating film, the optical density is preferably smaller than the above value.
[0432] In this specification, as a method for measuring the optical density of a cured film, first, a cured film is formed on a glass substrate, and the optical density per a predetermined film thickness is calculated using a spectrophotometer (UV-3600 manufactured by Hitachi, LTD., etc.).
[0433] Furthermore, even in the state of the composition layer (dried film) obtained by applying the composition and drying it, the film thickness and optical density generally do not change significantly compared to the state of the cured film obtained by subsequently exposing and curing it. In this case, the optical density of the composition layer (dried film) can be measured using the above-mentioned measurement method, and the obtained value can be used as the optical density of the cured film.
[0434] The film thickness of the cured film is preferably, for example, 0.1 to 4.0 μm, more preferably 1.0 to 2.5 μm. Depending on the application, the cured film may be a thin film or a thick film compared to this range.
[0435] In addition, the "light shielding" when the cured film formed from the composition of the present invention is used as a light shielding film also includes the concept of attenuating light while passing through the cured film (light shielding film). When the cured film (light shielding film) is used as a light attenuating film having such a function, the optical density of the cured film may be less than the above range.
[0436] Furthermore, when the cured film is used as a light attenuating film, the light shielding property can be adjusted by using a thinner film (e.g., 0.1 to 0.5 μm) than the above range. In this case, the optical density per 1.0 μm film thickness in the wavelength region of 400 to 700 nm (and / or light with a wavelength of 940 nm) is preferably 0.1 to 1.5, more preferably 0.2 to 1.0.
[0437] The reflectance of the cured film is preferably less than 8%, more preferably less than 6%, and further preferably less than 4%. The lower limit is 0% or more.
[0438] The reflectivity referred to here is obtained by using a VAR unit of a spectrometer V7200 (product name) manufactured by JASCO Corporation to inject light with a wavelength of 400 to 1100 nm at an incident angle of 5°, and obtaining the reflectivity spectrum obtained. Specifically, the reflectivity of light with a wavelength showing the maximum reflectivity within the wavelength range of 400 to 1100 nm is set as the reflectivity of the cured film.
[0439] Furthermore, the above-mentioned cured film is suitable for portable devices such as personal computers, tablet computers, mobile phones, smart phones and digital cameras; OA (Office Automation) equipment such as multi-function printers and scanners; industrial equipment such as surveillance cameras, barcode readers and automatic teller machines (ATMs), high-speed cameras and equipment with personal identification functions using face recognition or biometrics; vehicle-mounted camera equipment; medical camera equipment such as endoscopes, capsule endoscopes and catheters; and aerospace equipment such as living body sensors, biosensors (Biosensors), military reconnaissance cameras, stereo map cameras, meteorological and ocean observation cameras, land resource reconnaissance cameras, and astronomical and deep space target exploration cameras in the universe; etc.; and is suitable for light-shielding components and light-shielding films of optical filters and modules used in the above-mentioned devices, and is further suitable for anti-reflection components and anti-reflection films.
[0440] The cured film can also be used for micro LED (Light Emitting Diode) and micro OLED (Organic Light Emitting Diode) etc. In addition to optical filters and optical films used in micro LED and micro OLED, the cured film is also suitable for components that provide light shielding function or anti-reflection function.
[0441] Examples of micro LEDs and micro OLEDs include those described in Japanese Unexamined Patent Application Publication No. 2015-500562 and Japanese Unexamined Patent Application Publication No. 2014-533890.
[0442] The above-mentioned cured film is also preferably used as an optical and optical film for quantum dot sensors and quantum dot solid-state imaging elements. In addition, it is suitable as a member that imparts a light shielding function and an anti-reflection function. As quantum dot sensors and quantum dot solid-state imaging elements, for example, examples described in the specification of U.S. Patent Application Publication No. 2012 / 37789 and the brochure of International Publication No. 2008 / 131313 can be cited.
[0443] [Light-shielding film, optical element, solid-state imaging element, and solid-state imaging device]
[0444] The cured film of the present invention is also preferably used as a so-called light-shielding film. Such a light-shielding film is also preferably used for a solid-state imaging element.
[0445] As described above, the cured film formed using the light-shielding composition of the present invention is excellent in light-shielding property and low reflectivity.
[0446] In addition, a light-shielding film is one of the preferred uses of the cured film of the present invention, and the light-shielding film of the present invention can be produced by the method described as the method for producing the cured film. Specifically, the composition can be applied on a substrate to form a composition layer, and then exposed and developed to produce the light-shielding film.
[0447] The present invention also includes the invention of an optical element. The optical element of the present invention is an optical element having the above-mentioned cured film (light shielding film). As an optical element, for example, an optical element used in optical equipment such as a camera, binoculars, a microscope, and a semiconductor exposure device can be cited.
[0448] Among them, as the optical element, for example, a solid-state imaging element mounted on a camera or the like is preferable.
[0449] Furthermore, the solid-state imaging element of the present invention is a solid-state imaging element including the above-mentioned cured film (light shielding film) of the present invention.
[0450] As a form in which the solid-state imaging element of the present invention contains a cured film (light-shielding film), for example, a light-receiving element formed of a plurality of photodiodes and polycrystalline silicon, etc., which constitute a light-receiving area of a solid-state imaging element (CCD image sensor, CMOS image sensor, etc.) is provided on a substrate, and a cured film is provided on the light-receiving element formation surface side of the support body (for example, a portion other than the light-receiving portion and / or pixels for adjusting color, etc.) or on the side opposite to the formation surface.
[0451] Furthermore, when the cured film is used as a light attenuation film, for example, the dynamic range of the solid-state imaging element can be improved by arranging the light attenuation film so that part of the light enters the light receiving element after passing through the light attenuation film.
[0452] A solid-state imaging device includes the above-mentioned solid-state imaging element.
[0453] refer to Figure 1-2 , a structural example of a solid-state imaging device and a solid-state imaging element is described. Figure 1-2 In order to make each part clear, the ratio of thickness and / or width to each other is ignored and a part is exaggeratedly displayed.
[0454] Figure 1 It is a schematic cross-sectional view showing a structural example of a solid-state imaging device including the solid-state imaging element of the present invention.
[0455] like Figure 1 As shown, the solid-state imaging device 100 includes a rectangular solid-state imaging element 101, and a transparent cover glass 103 that is held above the solid-state imaging element 101 and seals the solid-state imaging element 101. Furthermore, a lens layer 111 is overlapped and provided on the cover glass 103 via a spacer 104. The lens layer 111 is composed of a support body 113 and a lens material 112. The lens layer 111 may be a structure in which the support body 113 and the lens material 112 are integrally formed. If stray light is incident on the peripheral region of the lens layer 111, the focusing effect of the lens material 112 is weakened due to the diffusion of light, and the light reaching the imaging unit 102 is reduced. In addition, noise caused by stray light is also generated. Therefore, a light shielding film 114 is provided on the peripheral region of the lens layer 111 to shield light. The cured film of the present invention can also be used as the above-mentioned light shielding film 114.
[0456] The solid-state imaging element 101 performs photoelectric conversion on an optical image formed on an imaging unit 102 serving as a light receiving surface thereof and outputs the image as an image signal. The solid-state imaging element 101 includes a stacked substrate 105 formed by stacking two substrates. The stacked substrate 105 is formed by a rectangular wafer substrate 106 and a circuit substrate 107 of the same size, and the circuit substrate 107 is stacked on the back of the wafer substrate 106.
[0457] As a material of a substrate used as the wafer substrate 106 , for example, a known material can be used.
[0458] The imaging unit 102 is provided at the center of the surface of the wafer substrate 106. In addition, a light shielding film 115 is provided in the peripheral region of the imaging unit 102. The light shielding film 115 shields stray light incident on the peripheral region, thereby preventing dark current (noise) from being generated in the circuit in the peripheral region. The cured film of the present invention is preferably used as the light shielding film 115.
[0459] A plurality of electrode pads 108 are provided on the edge of the surface of the wafer substrate 106 . The electrode pads 108 are electrically connected to the imaging unit 102 via signal lines (which may be bonding wires) provided on the surface of the wafer substrate 106 (not shown).
[0460] On the back side of the circuit substrate 107, external connection terminals 109 are provided substantially below each electrode pad 108. Each external connection terminal 109 is connected to the electrode pad 108 via a through electrode 110 vertically penetrating the laminated substrate 105. Furthermore, each external connection terminal 109 is connected to a control circuit for controlling the driving of the solid-state imaging element 101 and an image processing circuit for performing image processing on an imaging signal output from the solid-state imaging element 101 via wiring (not shown).
[0461] Figure 2 1 is a schematic cross-sectional view of the imaging unit 102. Figure 2 As shown, the imaging unit 102 is composed of a light receiving element 201, a color filter 202, a micro lens 203 and other components provided on a substrate 204. The color filter 202 has a blue pixel 205b, a red pixel 205r, a green pixel 205g and a black matrix 205bm. The cured film of the present invention can be used as the black matrix 205bm.
[0462] As the material of the substrate 204, for example, the same material as the wafer substrate 106 can be used. A p-hole layer 206 is formed on the surface of the substrate 204. In the p-hole layer 206, light receiving elements 201 formed of an n-type layer and generating and accumulating signal charges by photoelectric conversion are arranged in a square lattice.
[0463] On one side of the light receiving element 201, a vertical transfer path 208 formed of an n-type layer is formed via a readout gate portion 207 of the surface layer of the p-hole layer 206. Also, on the other side of the light receiving element 201, a vertical transfer path 208 belonging to an adjacent pixel is formed via an element isolation region 209 formed of a p-type layer. The readout gate portion 207 is a channel region for reading out the signal charge accumulated in the light receiving element 201 to the vertical transfer path 208.
[0464] A gate insulating film 210 formed of an ONO (Oxide-Nitride-Oxide) film is formed on the surface of the substrate 204. A vertical transfer electrode 211 formed of polysilicon or amorphous silicon is formed on the gate insulating film 210 so as to cover the vertical transfer path 208, the read gate portion 207, and substantially directly above the element isolation region 209. The vertical transfer electrode 211 functions as a driving electrode for driving the vertical transfer path 208 to transfer charges and a readout electrode for driving the readout gate portion 207 to read out signal charges. The signal charges are sequentially transferred from the vertical transfer path 208 to the horizontal transfer path and the output portion (floating diffusion amplifier) not shown, and then output as a voltage signal.
[0465] A light shielding film 212 is formed on the vertical transfer electrode 211 to cover the surface thereof. The light shielding film 212 has an opening just above the light receiving element 201 and shields the other regions from light. The cured film of the present invention can also be used as the light shielding film 212.
[0466] A transparent intermediate layer is provided on the light shielding film 212. The intermediate layer is formed of an insulating film 213 formed of BPSG (borophospho silicate glass), an insulating film (passivation film) 214 formed of P-SiN, and a planarizing film 215 formed of a transparent resin or the like. The color filter 202 is formed on the intermediate layer.
[0467] 〔Image display device〕
[0468] The image display device of the present invention includes the cured film of the present invention.
[0469] As an embodiment in which the image display device has a cured film, for example, there can be mentioned an embodiment in which the cured film is contained in a black matrix and a color filter including such a black matrix is used in the image display device.
[0470] Next, a black matrix and a color filter including the black matrix will be described, and further, a liquid crystal display device including such a color filter will be described as a specific example of an image display device.
[0471] <Black Matrix>
[0472] The cured film of the present invention is also preferably included in a black matrix. A black matrix may be included in an image display device such as a color filter, a solid-state imaging element, and a liquid crystal display device.
[0473] As the black matrix, for example, the above-mentioned black edges provided at the peripheral part of an image display device such as a liquid crystal display device, a grid-shaped and / or linear black portion between red, blue and green pixels, a dot-shaped and / or linear black pattern used for TFT (thin film transistor) light shielding, etc. The definition of the black matrix is described in, for example, Taihei Kanno, "Dictionary of Terms for Liquid Crystal Display Manufacturing Equipment", 2nd edition, NIKKAN KOGYOSHIMBUN, LTD., 1996, p. 64.
[0474] In order to improve display contrast and prevent image quality degradation caused by light leakage current in the case of an active matrix driven liquid crystal display device using thin film transistors (TFT), the black matrix preferably has high light shielding properties (optical density OD of 3 or more).
[0475] As a method for manufacturing a black matrix, for example, it can be manufactured using the same method as the method for manufacturing the above-mentioned cured film. Specifically, the composition can be applied on a substrate to form a composition layer, and a patterned cured film (black matrix) is manufactured by exposure and development. In addition, the film thickness of the cured film used as the black matrix is preferably 0.1 to 4.0 μm.
[0476] The material of the substrate preferably has a transmittance of 80% or more for visible light (wavelength 400 to 800 nm). Examples of such materials include glasses such as soda-lime glass, alkali-free glass, quartz glass, and borosilicate glass; plastics such as polyester resins and polyolefin resins; and the like. From the viewpoint of chemical resistance and heat resistance, alkali-free glass or quartz glass is preferred.
[0477] <Color Filter>
[0478] The cured film of the present invention is also preferably included in a color filter.
[0479] As a form of a color filter containing a cured film, for example, a color filter including a substrate and the above-mentioned black matrix can be cited. That is, a color filter including red, green and blue colored pixels formed in the openings of the above-mentioned black matrix formed on the substrate can be exemplified.
[0480] A color filter including a black matrix (cured film) can be produced by, for example, the following method.
[0481] First, a coating film (composition layer) of a composition containing a pigment corresponding to each color pixel of the color filter is formed in the opening of the patterned black matrix formed on the substrate. In addition, as the composition for each color, it is preferred that a known composition can be used, and among the compositions described in this specification, a composition in which the black color material is replaced with a colorant corresponding to each pixel is used.
[0482] Next, the composition layer is exposed via a photomask having a pattern corresponding to the opening of the black matrix. After that, the unexposed portion can be removed by development treatment, and then baked to form colored pixels at the opening of the black matrix. For example, as long as a series of operations are performed using each color composition containing red, green and blue pigments, a color filter having red, green and blue pixels can be manufactured.
[0483] <Liquid crystal display device>
[0484] The cured film of the present invention is also preferably included in a liquid crystal display device. As an embodiment in which a liquid crystal display device includes a cured film, for example, an embodiment including a color filter including the black matrix (cured film) described above can be cited.
[0485] The liquid crystal display device of the present embodiment may include, for example, a pair of substrates disposed opposite to each other and a liquid crystal compound sealed between the substrates. The substrates may be, for example, the substrates described above as black matrix substrates.
[0486] As a specific form of the above-mentioned liquid crystal display device, for example, there can be cited a stacked body containing, in order from the user side, polarizer / substrate / color filter / transparent electrode layer / alignment film / liquid crystal layer / alignment film / transparent electrode layer / TFT (Thin Film Transistor) element / substrate / polarizer / backlight unit.
[0487] In addition, as a liquid crystal display device, for example, a liquid crystal display device described in "Electronic Display Device (written by Akio Sasaki, published by Kogyo Chosakai Publishing Co., Ltd. in 1990)", "Display Device (written by Junsho Ibuki, published by Sangyo Tosho Publishing Co., Ltd. in 1989)" and the like can be cited. In addition, for example, a liquid crystal display device described in "Next Generation Liquid Crystal Display Technology (written by Tatsuo Uchida, published by Kogyo Chosakai Publishing Co., Ltd. in 1994)" can be cited.
[0488] 〔Infrared sensor〕
[0489] The cured film of the present invention is also preferably included in an infrared sensor.
[0490] use Figure 3 The infrared sensor of the above-mentioned embodiment will be described. Figure 3 It is a schematic cross-sectional view showing a structural example of an infrared sensor including the cured film of the present invention. Figure 3 The infrared sensor 300 shown includes a solid-state imaging element 310 .
[0491] The imaging region provided in the solid-state imaging element 310 is constituted by combining an infrared absorption filter 311 and a color filter 312 according to the embodiment of the present invention.
[0492] The infrared absorption filter 311 is a film that transmits light in the visible light region (e.g., light with a wavelength of 400 to 700 nm) and blocks light in the infrared region (e.g., light with a wavelength of 800 to 1300 nm, preferably light with a wavelength of 900 to 1200 nm, and more preferably light with a wavelength of 900 to 1000 nm). A cured film containing an infrared absorber (the form of the infrared absorber is as described above) can be used as a colorant.
[0493] The color filter 312 is a color filter formed with pixels that transmit and absorb light of specific wavelengths in the visible light region. For example, a color filter formed with red (R), green (G), and blue (B) pixels is used, and its form is as described above.
[0494] A resin film 314 (for example, a transparent resin film) that can transmit light having a wavelength of the infrared transmission filter 313 is disposed between the infrared transmission filter 313 and the solid-state imaging element 310 .
[0495] The infrared transmission filter 313 is a filter that has visible light shielding properties and transmits infrared light of a specific wavelength, and can use the cured film of the present invention containing a colorant that absorbs light in the visible light region (e.g., perylene compounds and / or bisbenzofuranone compounds, etc.) and an infrared absorber (e.g., pyrrolopyrrole compounds, phthalocyanine compounds, naphthalocyanine compounds, and polymethine compounds, etc.). The infrared transmission filter 313 preferably shields light of a wavelength of 400 to 830 nm and transmits light of a wavelength of 900 to 1300 nm.
[0496] A microlens 315 is disposed on the incident light hv side of the color filter 312 and the infrared transmission filter 313. A planarization film 316 is formed so as to cover the microlens 315.
[0497] exist Figure 3 In the illustrated embodiment, the resin film 314 is provided, but the infrared transmission filter 313 may be formed instead of the resin film 314. That is, the infrared transmission filter 313 may be formed on the solid-state imaging element 310.
[0498] And, in Figure 3 In the illustrated embodiment, the film thickness of the color filter 312 is the same as the film thickness of the infrared transmission filter 313, but the film thicknesses of the two may be different.
[0499] And, in Figure 3 In the form shown, the color filter 312 is arranged at a position closer to the incident light hv side than the infrared absorption filter 311, but the order of the infrared absorption filter 311 and the color filter 312 can also be swapped, and the infrared absorption filter 311 can be arranged at a position closer to the incident light hv side than the color filter 312.
[0500] And, in Figure 3In the embodiment shown, the infrared absorption filter 311 and the color filter 312 are stacked adjacent to each other, but the two filters do not necessarily need to be adjacent to each other, and another layer may be provided between the two filters. In addition to being used as a light shielding film on the end and / or side of the surface of the infrared absorption filter 311, the cured film of the present invention can also be used as an inner wall of an infrared sensor device to prevent accidental light from entering the internal reflection and / or improve the sensitivity of the light receiving part.
[0501] According to the infrared sensor, since image information can be read at the same time, motion sensing of an object that is detecting motion can be performed, etc. Furthermore, according to the infrared sensor, distance information can be acquired, so that images containing 3D information can be photographed, etc. Furthermore, the infrared sensor can also be used as a biometric sensor.
[0502] Next, a solid-state imaging device to which the above-mentioned infrared sensor is applied will be described.
[0503] The solid-state imaging device includes a lens optical system, a solid-state imaging element, an infrared light emitting diode, etc. For each structure of the solid-state imaging device, reference can be made to paragraphs 0032 to 0036 of Japanese Patent Application Laid-Open No. 2011-233983, and the contents are incorporated into this specification.
[0504] 〔Headlight unit〕
[0505] The cured film of the present invention is also preferably included as a light shielding film in a headlight unit for a vehicle such as an automobile. The cured film of the present invention included as a light shielding film in a headlight unit is preferably formed in a pattern to shield at least a part of light emitted from a light source.
[0506] use Figure 4 and Figure 5 The headlight unit according to the above-mentioned embodiment will be described. Figure 4 is a schematic diagram showing a structural example of a headlight unit, Figure 5 It is a schematic perspective view showing a structural example of a light shielding portion of a headlight unit.
[0507] like Figure 4 As shown, the headlight unit 10 includes a light source 12 , a light shielding portion 14 , and a lens 16 , and the light source 12 , the light shielding portion 14 , and the lens 16 are arranged in this order.
[0508] like Figure 5 As shown, the light shielding portion 14 includes a base 20 and a light shielding film 22 .
[0509] The light shielding film 22 is provided with a patterned opening 23 for irradiating light emitted from the light source 12 in a specific shape. The light distribution pattern irradiated from the lens 16 is determined by the shape of the opening 23 of the light shielding film 22. The lens 16 projects the light L from the light source 12 that has passed through the light shielding portion 14. As long as a specific light distribution pattern can be irradiated from the light source 12, the lens 16 is not necessarily required. The lens 16 is appropriately determined according to the irradiation distance and irradiation range of the light L.
[0510] The structure of the base 20 is not particularly limited as long as it can hold the light shielding film 22 , but is preferably not deformed by heat from the light source 12 , and is, for example, made of glass.
[0511] Figure 5 An example of a light distribution pattern is shown in FIG. , but the present invention is not limited to this.
[0512] Furthermore, the light source 12 is not limited to one, and can be arranged in a row or in a matrix. When multiple light sources are provided, for example, one light shielding portion 14 can be provided for one light source 12. In this case, the light shielding films 22 of the multiple light shielding portions 14 can all have the same pattern or different patterns.
[0513] The light distribution pattern based on the pattern of the light shielding film 22 will be described.
[0514] Figure 6 is a schematic diagram showing an example of a light distribution pattern based on a headlight unit, Figure 7 is a schematic diagram showing another example of a light distribution pattern based on a headlight unit. Figure 6 The light distribution pattern 30 and Figure 7 The light distribution patterns 32 shown all represent areas where light is irradiated. Figure 6 The area 31 and Figure 7 The areas 31 shown in the figure all represent the case where the light shielding film 22 is not provided, and the light source 12 (reference Figure 4 ) irradiated area.
[0515] For example, Figure 6 In the light distribution pattern 30 shown, the light intensity drops sharply at the edge 30a due to the pattern of the light shielding film 22. For example, Figure 6 The light distribution pattern 30 shown is a pattern that does not irradiate light toward an oncoming vehicle when the vehicle is traveling to the left.
[0516] And, if Figure 7 The light distribution pattern 32 shown can also be set to Figure 6 The light distribution pattern 30 shown in FIG. Figure 6The light distribution pattern 30 shown is the same. The intensity of light drops sharply at the edge 32a, for example, forming a pattern where light is not irradiated to the oncoming vehicle when driving on the left. Furthermore, the intensity of light also drops sharply at the notch 33. Therefore, in the region 34 corresponding to the notch 33, for example, signs indicating states such as a curved road, uphill, or downhill can be displayed. Thus, the safety during night driving can be improved.
[0517] In addition, the light-shielding part 14 is not limited to being fixedly arranged between the light source 12 and the lens 16, and can also be configured to be arranged between the light source 12 and the lens 16 as needed by a driving mechanism (not shown) to obtain a specific light distribution pattern.
[0518] Moreover, the light-shielding part 14 can also be constituted by a light-shielding member capable of blocking the light from the light source 12. At this time, it can also be configured to be arranged between the light source 12 and the lens 16 as needed by a driving mechanism (not shown) to obtain a specific light distribution pattern.
[0519] Embodiment
[0520] Hereinafter, the present invention will be further described in detail based on embodiments. The materials, amounts used, ratios, treatment contents, treatment steps, etc. shown in the following embodiments can be appropriately changed as long as they do not depart from the gist of the present invention. Therefore, the scope of the present invention should not be construed in a limiting manner by the embodiments shown below.
[0521] <<Test X>>
[0522] [Manufacture of Composition]
[0523] Hereinafter, each component used in the preparation of the composition will be described.
[0524] [Particles]
[0525] The particles manufactured by the method shown below are used in the preparation of the composition.
[0526] In addition, the following particles all correspond to black pigments.
[0527] [Manufacture of Zr Particles Z-1]
[0528] Particles containing zirconium (hereinafter also referred to as "Zr particles") Z-1 were manufactured using a device based on the black composite particle manufacturing device described in International Publication No. 2010 / 147098. Figure 1 as described in
[0529] In a black composite particle manufacturing apparatus, a high-frequency voltage of approximately 4 MHz and approximately 80 kVA is applied to the high-frequency oscillation coil of a plasma torch, and a mixed gas of 50 L / min of argon and 50 L / min of nitrogen is supplied from a plasma gas supply source as the plasma gas, thereby generating an argon-nitrogen thermal plasma flame in the plasma torch. Further, 10 L / min of a carrier gas is supplied from the jet gas supply source of the material supply apparatus.
[0530] Then, zirconium chloride (white powder, manufactured by FUJIFILM Wako Pure Chemical Corporation), additive particles (Fe powder manufactured by JFE Steel Corporation, JIP270M, particle size 150 μm or less), liquid ammonia (manufactured by Ube Industries, Ltd.), and argon as the carrier gas are supplied together into the thermal plasma flame in the plasma torch, and are thus evaporated in the thermal plasma flame and highly dispersed in the gas phase. In addition, the addition amount of the above additive particles is set to 0.05 mass% with respect to 100 mass% of the total mass of zirconium chloride and the additive particles.
[0531] Further, nitrogen is used as the gas supplied into the chamber through the gas supply apparatus. The flow rate in the chamber at this time is set to 5 m / sec, and the supply amount is set to 1000 L / min. Further, the pressure in the cyclone is set to 50 kPa, and the supply rate of zirconium chloride and the additive particles from the chamber to the cyclone is set to 10 m / s (average value).
[0532] Then, for the particles obtained using the black composite particle manufacturing apparatus, heat treatment was performed using LABOKILN L / K manufactured by Narahashi Seisakusho Co., Ltd. as a calcination furnace. Specifically, nitrogen was supplied into the calcination furnace at 100 mL / min as an atmosphere gas, and heat treatment was performed at 240°C for 3 hours.
[0533] Zr particles Z-1 were obtained as above. Z-1 is oxynitride zirconium particles.
[0534] <Manufacture of Zr particles Z-2 to Z-12, Z-15, Z-16, ZZ-1, ZZ-2>
[0535] In the manufacturing method of the above Z-1, except that the addition amount of the additive particles and the heat treatment conditions are as described in Table 1 in the following section, Zr particles Z-2 to Z-12, Z-15, Z-16, ZZ-1, and ZZ-2 were similarly manufactured. Zr particles Z-2 to Z-12, Z-15, Z-16, ZZ-1, and ZZ-2 are all oxynitride zirconium particles.
[0536] <Manufacture of Zr particles Z-13 (particles having a coating layer formed of silica)>
[0537] To 0.1 mol of the above Z-2, 12 mol of ethanol was added as an alcohol, and Z-2 was dispersed in ethanol and wet pulverized by a bead mill to obtain a dispersion of Z-2. Then, after adding 6 mol of ethanol for concentration adjustment to this dispersion of Z-2, 1×10 -2 mol of tetramethyl orthosilicate was added as a silica source for forming a silica film. Next, 1×10 -3 mol of sodium hydroxide was added as a base source (reaction initiator) to the dispersion of Z-2 to which the tetramethyl orthosilicate had been added, and the reaction was initiated in the dispersion. Further, after washing and drying the dispersion, it was calcined to obtain Zr particles Z-13 having a core coated with a silica film.
[0538] In addition, regarding the washing of the above dispersion, in order to remove impurities from the dispersion, after passing the dispersion through a centrifugal separator, the dispersion was passed through a filter made of an ion exchange resin. And the above calcination was a treatment of maintaining at 350 °C for 5 hours in a nitrogen atmosphere.
[0539] The content of the metal oxide (metal oxide coating layer formed of silica) in Z-13 is 5% by mass relative to the total mass of Z-13.
[0540] <Manufacture of Zr particles Z-14 (particles having a coating layer formed of alumina)>
[0541] The above Z-2 was mixed with water, and using a sand mill, it was adjusted to an aqueous slurry having a weight of 100 g / liter as Z-2 powder to obtain an aqueous dispersion having a powder concentration of 100 g / liter. While stirring the slurry, it was heated to 60 °C, and while maintaining this temperature, while maintaining the pH of the above aqueous slurry at 7.0, an aqueous sodium aluminate solution and a dilute sulfuric acid solution were added simultaneously for 30 minutes, and aging was continued for 30 minutes.
[0542] After that, the obtained neutralization reaction product was filtered and washed, and dried at a temperature of 120 °C for 5 hours to obtain Zr particles Z-14 having a core coated with an alumina film.
[0543] In addition, the addition amount of the aqueous sodium aluminate solution was adjusted to be in the range of 0.1 to 25 parts by mass as Al2O3 relative to 100 parts by mass of Z-2, and the content of the metal oxide (metal oxide coating layer formed of alumina) relative to the total mass of the finally obtained Z-14 became 5% by mass.
[0544] Regarding each of the obtained Zr particles, the contents of zirconium (Zr) atoms, iron (Fe) atoms, and chlorine (Cl) atoms were measured by ICP emission spectrometry. In addition, an ICP emission spectrometry apparatus "SPS3000" (product name) manufactured by Seiko Instruments Inc. was used in the ICP emission spectrometry.
[0545] Also, similarly, regarding the obtained Zr particles, the content of nitrogen atoms was measured. Regarding the content of nitrogen atoms, measurement was carried out using an oxygen / nitrogen analyzer "EMGA-620W / C" (product name) manufactured by HORIBA, Ltd., and calculation was performed by the inert gas fusion thermal conductivity method. The results are shown in Table 1.
[0546] The manufacturing conditions and analysis results of each Zr particle are shown in the following table.
[0547] In addition, in the following table, Zr particles Z-1 to Z-16 are specific particles.
[0548] In the table, the "addition amount" column in the "added particles" column and the "addition amount" column in the "zirconium chloride" column respectively represent the ratio of the content of each component to 100% by mass of the total mass of zirconium chloride and added particles when manufacturing the Zr particles.
[0549] The "heat treatment conditions" column represents the temperature and time of heat treatment when performing heat treatment by a calcination furnace.
[0550] The "coating layer" column represents the presence or absence of a coating layer or the material of the coating layer in each Zr particle.
[0551] The "Fe atom / Cl atom" column represents the mass ratio of the content of Fe atoms to the content of Cl atoms in each Zr particle (mass of contained Fe atoms / mass of contained Cl atoms).
[0552] The "atomic composition" column represents the content (mass%) of each atom in each Zr particle relative to the total mass of the Zr particle. In each Zr particle, more than 80% by mass of the remaining components other than Zr atoms, N atoms, Fe atoms, and Cl atoms are oxygen atoms.
[0553] In addition, the average primary particle size of each Zr particle is in the range of 20 to 30 nm.
[0554] [Table 1]
[0555]
[0556] <Manufacture of <Ti particles (particles containing titanium) Ti-1>
[0557] 100 g of titanium oxide MT-150A (product name: manufactured by TAYCA CORPORATION) with an average primary particle size of 15 nm and 25 g of a BET surface area of 300 m 2 / g of silica particles AEROPERL (registered trademark) 300 / 30 (manufactured by EVONIK) and 100 g of a dispersant Disperbyk 190 (product name: manufactured by BYK-Chemie GmbH) were added to 71 g of ion-exchanged water to obtain a mixture.
[0558] Afterwards, the mixture was treated for 20 minutes at a revolution speed of 1360 rpm and a rotation speed of 1047 rpm using MAZERSTAR KK-400W manufactured by KURABO to obtain a mixed solution. The mixed solution was filled in a quartz container and heated to 920°C in an oxygen atmosphere using a small rotary kiln (manufactured by Motoyama Co., Ltd.). Afterwards, the atmosphere in the small rotary kiln was replaced with nitrogen, and ammonia was allowed to flow in the small rotary kiln at 100 mL / min for 5 hours at the same temperature to implement a nitriding reduction treatment. The powder recovered after the completion was crushed using a mortar to obtain a powdered titanium black Ti-1 containing Si atoms. The dispersed body containing titanium black (titanium oxynitride) particles and Si atoms was obtained. The specific surface area obtained was: 73 m 2 / g〕.
[0559] <Carbon Black CB-1>
[0560] Carbon black manufactured by Degussa AG, namely “Color Black S170 (product name, average primary particle size 17 nm, BET specific surface area 200 m 2 / g, carbon black produced by gas black method)" is designated as carbon black CB-1.
[0561] 〔Dispersant〕
[0562] The following dispersants were used.
[0563] Dispersant A
[0564] Dispersant A is a dispersant produced by the production method shown below.
[0565] ··Synthesis Example A1: Synthesis of Macromonomer A-1
[0566] ε-caprolactone (1044.2 g), δ-valerolactone (184.3 g) and 2-ethyl-1-hexanol (71.6 g) were introduced into a 3000 mL three-necked flask to obtain a mixture. Then, the mixture was stirred while blowing nitrogen. Then, Disperbyk111 (12.5 g, manufactured by BYK-Chemie GmbH, phosphoric acid resin) was added to the mixture, and the obtained mixture was heated to 90° C. After 6 hours, the mixture was heated to 100° C. using a 1% ethanol solution. 1 After confirming the disappearance of the signal derived from 2-ethyl-1-hexanol in the mixture by H-NMR (nuclear magnetic resonance), the mixture was heated to 110° C. The polymerization reaction was continued at 110° C. for 12 hours under nitrogen. 1 H-NMR confirmed the disappearance of the signals derived from ε-caprolactone and δ-valerolactone, and the molecular weight of the obtained compound was measured by GPC (Gel permeation chromatography). After confirming that the molecular weight of the compound reached the desired value, 2,6-di-tert-butyl-4-methylphenol (0.35 g) was added to the mixture containing the above compound, and 2-methacryloyloxyethyl isocyanate (87.0 g) was further added to the obtained mixture over 30 minutes. Six hours after the addition was completed, the molecular weight of the obtained compound was measured by using the method of HPLC. 1 After H-NMR confirmed that the signal derived from 2-methacryloyloxyethyl isocyanate (MOI) disappeared, propylene glycol monomethyl ether acetate (PGMEA) (1387.0 g) was added to the mixture to obtain a macromonomer A-1 solution (2770 g) with a concentration of 50% by mass. The obtained macromonomer A-1 had a weight average molecular weight of 6,000.
[0567] ··Synthesis Example P-1: Synthesis of Dispersant A
[0568] Into a three-necked flask with a capacity of 1000 mL, macromonomer A-1 (200.0 g), methacrylic acid (hereinafter also referred to as "MAA", 60.0 g), benzyl methacrylate (hereinafter also referred to as "BzMA", 40.0 g), and PGMEA (propylene glycol 1-monomethyl ether 2-acetate, 366.7 g) were introduced to obtain a mixture. The above mixture was stirred while blowing nitrogen. Then, the mixture was heated to 75°C while nitrogen was flowing in the flask. Next, dodecyl mercaptan (5.85 g) was added to the mixture, followed by 2,2'-azobis(methyl 2-methylpropionate) (1.48 g, hereinafter also referred to as "V-601") to initiate a polymerization reaction. After the mixture was heated at 75°C for 2 hours, V-601 (1.48 g) was further added to the mixture. After 2 hours, V-601 (1.48 g) was further added to the mixture. After further reacting for 2 hours, the mixture was heated to 90° C. and stirred for 3 hours. The polymerization reaction was completed through the above operation, and a dispersant A was obtained.
[0569] Dispersant B
[0570] Dispersant B is a dispersant produced by the production method shown below.
[0571] Under air, tetrabutylammonium (TBAB, 7.5 g) and p-methoxyphenol (MEHQ, 0.13 g) were added to the solution of dispersant A obtained in Synthesis Example P-1, and then glycidyl methacrylate (GMA, 66.1 g) was added dropwise. After the addition was completed, the reaction was continued for 7 hours under air, and the end of the reaction was confirmed by acid value measurement. PGMEA (643.6 g) was added to the obtained mixture to obtain a 20% solution of dispersant B. The weight average molecular weight of the obtained dispersant B was 35,000, and the acid value was 50 mgKOH / mg.
[0572] The structures of dispersants C to H are shown below.
[0573] In the structural formulas of dispersants C to F, the numerical values indicated in the respective repeating units represent the mass ratios.
[0574] [Chemical formula 6]
[0575]
[0576] Dispersant I: solid content (resin) contained in LPN-21116 (product name, manufactured by BYK (solid content: 40 mass %)).
[0577] The solid content (resin) of the dispersant I is a resin containing the structural units (1a) to (3a) shown below, having an amine value of 75 mgKOH / g and an acid value of 0 mgKOH / g.
[0578] [Chemical formula 7]
[0579]
[0580] In addition, among the dispersants A to I, the dispersants A to G and I correspond to dispersants having a graft structure.
[0581] Dispersant G corresponds to a dispersant having a radial structure.
[0582] Among the dispersants A to I, the dispersants A to H correspond to dispersants containing an acid group.
[0583] The acid value (unit: mgKOH / g), amine value (unit: mgKOH / g), and molecular weight (weight average molecular weight) of the solid content of Dispersants A to I are as follows.
[0584]
[0585] 〔Resin (alkali soluble resin)〕
[0586] The following resins (alkali-soluble resins) were used.
[0587] A-1: Resin with the following structure (solid content 40%, solvent: propylene glycol monomethyl ether, the structure of the solid content (resin) refers to the following structure, and the composition ratio shown in the structure is a molar ratio, and the weight average molecular weight of the resin: 11000, the acid value of the resin: 70 mgKOH / g)
[0588] [Chemical formula 8]
[0589]
[0590] A-2: a copolymer of benzyl methacrylate and methacrylic acid in a ratio of 7:3 (molar ratio) (weight average molecular weight: 30,000, acid value: 112.8 mgKOH / g, PGMEA 40 mass % solution)
[0591] 〔Polymerizable compounds〕
[0592] The following polymerizable compounds were used.
[0593] M1: A mixture of compounds having the following structures (the composition ratios shown in the structures are mass ratios):
[0594] [Chemical formula 9]
[0595]
[0596] M2: A mixture of compounds having the following structures (the composition ratios shown in the structures are in mass %)
[0597] [Chemical formula 10]
[0598]
[0599] M3: Compounds with the following structures
[0600] [Chemical formula 11]
[0601]
[0602] M4: A mixture of compounds with the following structures
[0603] [Chemical formula 12]
[0604]
[0605] 〔Photopolymerization initiator〕
[0606] The photopolymerization initiators shown below were used. Among the polymerization initiators shown below, I-1 to I-8 are photopolymerization initiators of oxime compounds. I-9 is a photopolymerization initiator other than an oxime compound.
[0607] I-1: A polymerization initiator of the following formula (I-1)
[0608] I-2: Irgacure OXE01 (product name, manufactured by BASF Japan)
[0609] I-3: Irgacure OXE02 (product name, manufactured by BASF Japan)
[0610] I-4: A polymerization initiator of the following formula (I-4)
[0611] I-5: A polymerization initiator of the following formula (I-5)
[0612] I-6: A polymerization initiator of the following formula (I-6)
[0613] ·I-7: Adeka Arkls NCI-831 (manufactured by ADEKA CORPORATION)
[0614] I-8: N-1919 (manufactured by ADEKA CORPORATION)
[0615] I-9: Omnirad 907 (manufactured by IGM Resins BV)
[0616] [Chemical formula 13]
[0617]
[0618] 〔Surfactant〕
[0619] The surfactants shown below were used.
[0620] F-1: Surfactant represented by the following formula (weight average molecular weight (Mw) = 15311)
[0621] In the following formula, the structural unit represented by (A) accounts for 62 mol%, and the structural unit represented by (B) accounts for 38 mol%. In the structural unit represented by (B), a, b, and c satisfy the relationship of a+c=14 and b=17, respectively.
[0622] [Chemical formula 14]
[0623]
[0624] 〔Inhibitor〕
[0625] The following polymerization inhibitors were used.
[0626] PI-1: p-Methoxyphenol
[0627] 〔Organic solvent〕
[0628] The following organic solvents were used.
[0629] ·PGMEA: Propylene glycol monomethyl ether acetate
[0630] Cyclopentanone
[0631] [Preparation of Composition (Photosensitive Composition)]
[0632] A composition (photosensitive composition) was prepared by the method shown below.
[0633] <Preparation of Pigment Dispersion Liquid 1 (Dispersion Liquid 1)>
[0634] First, a pigment dispersion (dispersion liquid) was prepared.
[0635] The following components were mixed according to the following formulation to prepare a dispersion 1.
[0636] Particles: 25 parts by mass
[0637] · 30 mass % solution of any one of dispersants A to I: 25 mass parts
[0638] Cyclopentanone: 50 parts by mass
[0639] In addition, the above-mentioned "particles" are any one of the above-mentioned particles, or mixed particles obtained by mixing two kinds of particles. The composition of the mixed particles is a mixed particle obtained by mixing the above-mentioned Z-14 and Ti-1 at a mass ratio of Z-14 / Ti-1=70 / 30, or a mixed particle obtained by mixing the above-mentioned Z-14 and CB-1 at a mass ratio of Z-14 / CB-1=70 / 30, or a mixed particle obtained by mixing the above-mentioned Z-6 and Ti-1 at a mass ratio of Z-6 / Ti-1=70 / 30.
[0640] The above-mentioned “30 mass % solution of any one of the dispersants A to I” is a solution obtained by adding PGMEA so that the solid content (resin) concentration becomes 30 mass % with respect to the above-mentioned dispersants A to I.
[0641] (Dispersion conditions)
[0642] The mixture of the above components was subjected to a dispersion treatment under the following conditions using NPM-Pilot manufactured by Shinmaru Enterprises Corporation. This was used as a dispersion liquid 1.
[0643] · Microbead diameter: φ0.05mm, (zirconia beads manufactured by NIKKATO CORPORATION, YTZ)
[0644] Microsphere filling rate: 65 volume %
[0645] ·Grinding circumferential speed: 10m / sec
[0646] ·Separator circumferential speed: 13m / s
[0647] ·Amount of mixed liquid for dispersion treatment: 15kg
[0648] ·Circulation flow rate (pump supply): 90kg / hour
[0649] ·Processing liquid temperature: 45℃
[0650] Cooling water: water
[0651] Processing time: 22 hours
[0652] <Preparation of Composition>
[0653] The compositions of the respective test examples were prepared by mixing the dispersion 1, the alkali-soluble resin, the polymerizable compound, the polymerization initiator, the surfactant, the polymerization inhibitor, and the solid content concentration adjusting PGMEA so that the solid content concentration of the obtained composition was 32.5% by mass and the obtained composition satisfied the mass ratio of the solid content shown below.
[0654] In addition, below, even if it is a component added in a state of being dissolved in a solvent, the mass ratio of the added target itself relative to the total solid content in the composition is indicated. For example, when the alkali-soluble resin is A-1, A-1 is provided in the preparation of the composition in a state of being an alkali-soluble resin dissolved in an organic solvent, but in the following, the mass ratio of the resin component (solid content) of the alkali-soluble resin A-1 added as above is indicated.
[0655] In addition, in the preparation of the composition, two or more components of the same type are sometimes used. In this case, the following expression represents the mass ratio of the total of the two or more components of the same type. For example, the composition sometimes contains two or more particles. In this case, the total mass ratio of the two or more particles is 60.
[0656]
[0657]
[0658] [evaluate]
[0659] The composition of each example was subjected to the following evaluations.
[0660] [Viscosity stability over time (dispersion stability)]
[0661] 50 g of the composition just prepared was placed in a 100 mL glass container, which was sealed and left to stand for 7 days at 45° C. The viscosity change of the composition before and after standing was measured, and the viscosity stability (dispersion stability) over time was evaluated according to the following criteria.
[0662] The viscosity change was determined based on the viscosity before standing still as a standard (100%).
[0663] The viscosity was measured at 25° C. using a cone-plate viscometer (manufactured by Toki Sangyo Co., Ltd., model number RE-85L).
[0664] A: The change in viscosity is less than 5%.
[0665] B: The amount of change in viscosity is 5% or more and less than 10%.
[0666] C: The amount of change in viscosity is 10% or more and less than 15%.
[0667] D: The change in viscosity is 15% or more.
[0668] 〔Corrosion resistance of electrode〕
[0669] Each composition of the embodiment and the comparative example was applied to an electrode pattern (copper) formed on the surface of a silicon wafer using a spin coater so that the dry film thickness of the coating film was 0.7 μm. After coating, the coating film was left in this state for 10 minutes, and then the silicon wafer coated with each composition was heated (prebaked) for 120 seconds using a 100° C. hot plate to form a coating film.
[0670] Then, an i-ray stepper exposure device FPA-3000i5+ (manufactured by CANON ELECTRONICS INC.) was used to expose the film at a wavelength of 365 nm and 500 mJ / cm through a pattern mask having an island pattern of 20 μm square. 2 The coating film was exposed to an exposure amount of .
[0671] Thereafter, the silicon wafer with the exposed coating film was placed on a horizontal rotating table of a rotary spray developer (DW-30 model, manufactured by Chemitronics Co., Ltd.) and subjected to rotary immersion development at 23° C. for 60 seconds using CD-2000 (manufactured by FUJIFILM Electronic Materials Co., Ltd., organic alkaline solution developer).
[0672] Then, the silicon wafer after spin immersion development was fixed on the above-mentioned horizontal rotating table by vacuum suction cup, and the silicon wafer was rotated at a speed of 50 rpm by a rotating device, and pure water was supplied from the top of the rotation center by spraying from the nozzle to rinse. After that, the silicon wafer was dried by a sprayer, thereby producing a wafer with a frame-shaped black matrix.
[0673] After the wafer with the frame-shaped black matrix was stored for 3 months under the environment of temperature 25°C and humidity 65%RH, the number of rusted parts of the electrode pattern was observed by an optical microscope (manufactured by Olympus Corporation, product name "LEXT 0LS4500") for 300 electrode pads of the unexposed part formed on the wafer. The corrosion resistance of the electrode was evaluated according to the number of rusted parts and the following criteria.
[0674] A: There are 0 to 5 rusted areas
[0675] B: There are 6 to 10 rusted areas
[0676] C: There are 11 to 20 rusted areas
[0677] D: There are more than 21 rusted areas
[0678] [Pattern forming properties (development residue)]
[0679] Regarding a wafer having a frame-shaped black matrix obtained in the same manner as the above-mentioned "corrosion resistance of the electrode" test, the unexposed portion was observed using a scanning electron microscope (manufactured by Hitachi High-Technologies Corporation, product name "SU8010") at a magnification of 20,000 times, the number of particulate residues confirmed in the obtained observation image was counted, and the pattern forming property (development residue) was evaluated using the following criteria.
[0680] A: No development residue was observed in the unexposed area
[0681] B: 1 to 49 particles of development residue on the unexposed area
[0682] C: 50 to 100 particles of development residue on the unexposed area
[0683] D: There are 101 or more particle-shaped development residues on the unexposed part
[0684] 〔Light separation (light blocking)〕
[0685] By spin coating, each composition of the embodiment and the comparative example was applied on a glass plate (EagleXG, manufactured by Corning) with a thickness of 0.7 mm and a square of 10 cm at a rotation speed of 1.5 μm after drying to form a coating film. Then, using a hot plate, the coating film was heat-treated at 100°C for 2 minutes to obtain a dried film. The OD (optical density) of the obtained dried film was measured using a spectrophotometer U-4100 (manufactured by Hitachi High-Technologies Corporation). According to the minimum OD at a wavelength of 400 to 1200 nm, the spectral (light-shielding) was evaluated by the following benchmarks.
[0686] AA: minimum OD>3.5
[0687] A: 3.5≥minimum OD>3.0
[0688] B: 3.0≥minimum OD>2.5
[0689] C: 2.5≥minimum OD>2.0
[0690] D: 2.0 ≥ minimum OD
[0691] 〔Pattern Adhesion〕
[0692] The composition was applied to an 8-inch silicon wafer substrate by spin coating at a rotation speed capable of forming a cured film having an OD (optical density) of 3 with respect to light of a wavelength of 940 nm, thereby forming a coating film. The coating film was heat treated at 100° C. for 2 minutes on a hot plate to obtain a dried film. Then, an i-ray stepper exposure device FPA-5510iZa (manufactured by CANON ELECTRONICS INC.) was used, and a mask of a 20 μm×20 μm area was exposed at a wavelength of 365 nm at a rate of 500 mJ / cm 2 The dry film was exposed with an exposure amount of . Afterwards, the silicon wafer substrate with the exposed dry film was placed on a horizontal rotating table of a rotary spray developer (DW-30 model, manufactured by Chemitronics Co., Ltd.), and was subjected to 60 seconds of spin immersion development at 23°C using CD-2000 (manufactured by FUJIFILM Electronic Materials Co., Ltd., organic alkaline solution developer). Then, the silicon wafer substrate after spin immersion development was fixed on the above-mentioned horizontal rotating table by a vacuum suction cup, and the silicon wafer substrate was rotated at a rotation speed of 50 rpm by a rotating device, while pure water was supplied from a spray nozzle from above its rotation center in a spray state for rinsing treatment, thereby producing a silicon wafer substrate with a 20μm×20μm pattern formed on the substrate. The obtained pattern-forming substrate was heat-treated at 220° C. for 1 hour using a clean oven (High-temperature clean oven CLH-300S, manufactured by Koyo Thermo Systems Co., Ltd.) to obtain a cured film (cured film-attached substrate).
[0693] The obtained cured film (cured film-attached substrate) was observed by cross-sectional SEM (scanning electron microscope), and the adhesion of the pattern was evaluated based on the following criteria.
[0694] A: The width of the space between the cured film and the substrate (the width at which the cured film peels off) is less than 3 μm from the edge of the pattern.
[0695] B: The width of the space between the cured film and the substrate (the width at which the cured film peels off) is 3 μm or more and less than 5 μm from the pattern edge.
[0696] C: The width of the space between the cured film and the substrate (the width at which the cured film peels off) is 5 μm or more from the edge of the pattern.
[0697] D: The 20μm×20μm pattern was peeled off and could not be measured.
[0698] 〔Degassing〕
[0699] A frame for a color filter was produced using each composition of the Examples and Comparative Examples.
[0700] Specifically, on a semiconductor substrate composed of an 8-inch substrate assuming an image sensor, the composition of the embodiment and the comparative example was spin-coated to form a coating film so that the film thickness after pre-baking was 1.5 μm. Next, a binary mask capable of forming a light-shielding film with a width of 250 μm and a length of 200 μm on the periphery of 720 μm in width and 520 μm in length was arranged, and exposure (exposure amount 500 mJ / cm 2 ) and then further developed.
[0701] The semiconductor substrate having a plurality of frames for the obtained color filters was cut into a size of 10 mm × 10 mm, and the amount of Cl in the degassing was detected by temperature desorption gas analysis (TDS), and the evaluation was performed according to the following criteria. The count intensity ratio of the peak position derived from Cl in the total degassing amount (detected total ion current value) from mass number 1 to 199 when the count derived from the atmospheric components included in the background was eliminated was measured, and the evaluation was performed according to the following criteria. The vacuum degree during the measurement was set to 1×10 -7 Torr or less.
[0702] A: The amount of Cl in 1L of degassing is less than 10 volppm
[0703] B: The Cl content in 1L of degassing is more than 10 volppm and less than 50 volppm
[0704] C: In 1L of degassing, the Cl content exceeds 50 volume ppm and is less than 100 volume pμμm
[0705] D: The amount of Cl exceeds 100 vol ppm in 1 L of degassing
[0706] [result]
[0707] The following table shows the solid content formulation and characteristics of the composition used in each test example and the test results.
[0708] The "Zr" column, "N" column, "Fe" column, and "Cl" column in the "Characteristics of Zr-containing particles" column in the table represent the content (mass %) of each atom relative to the total mass of the Zr particles (zirconium-containing particles) used to prepare the composition.
[0709] The “Fe / Cl” column in the “Characteristics of Zr-Containing Particles” column indicates the mass ratio of the content of Fe atoms to the content of Cl atoms in the Zr particles used to prepare the composition (content mass of Fe atoms / content mass of Cl atoms).
[0710] The column "Oxime-based polymerization initiator" indicates whether the polymerization initiator used is an oxime-based polymerization initiator. When the polymerization initiator is an oxime-based polymerization initiator, it is set as "A", and when the polymerization initiator is not an oxime-based polymerization initiator, it is set as "B".
[0711] [Table 2]
[0712]
[0713] [Table 3]
[0714]
[0715] [Table 4]
[0716]
[0717] [Table 5]
[0718]
[0719] [Table 6]
[0720]
[0721] From the results shown in the table, it was confirmed that the subject of the present invention can be solved by using the composition of the present invention.
[0722] Among them, from the viewpoint of more excellent effects of the present invention, it was confirmed that the photopolymerization initiator is preferably an oxime compound, and more preferably a polymerization initiator represented by formula (I-1) (see comparison of the results of Examples 2 and 19 to 27, etc.)
[0723] From the viewpoint of achieving more excellent effects of the present invention, it was confirmed that the Cl atom content is preferably 0.001 to 0.300 mass % based on the total mass of the zirconium nitride-based particles (see comparison between Examples 11 and 12, comparison between Examples 8 and 13, etc.).
[0724] From the viewpoint of achieving more excellent effects of the present invention, it was confirmed that the zirconium nitride-based particles preferably contain 0.010 to 0.150 mass % of Fe atoms relative to the total mass of the zirconium nitride-based particles (see comparison with Examples 1 to 6, etc.).
[0725] From the viewpoint of achieving more excellent effects of the present invention, it was confirmed that the mass ratio of the content of Fe atoms to the content of Cl atoms (Fe / Cl) in the zirconium nitride-based particles is preferably 0.008 to 1.5 (see comparison between Examples 5 and 6, comparison between Examples 1 and 14, etc.).
[0726] From the viewpoint of further improving the effects of the present invention, it was confirmed that it is preferable to further contain a black pigment (see the results of Examples 17 and 18, etc.).
[0727] From the viewpoint of achieving more excellent effects of the present invention, it was confirmed that the amine value of the dispersant is preferably 0 to 25 mgKOH / g (see comparison of Examples 28 to 36, etc.).
[0728] From the viewpoint of achieving more excellent effects of the present invention, it has been confirmed that the zirconium nitride-based particles preferably contain: a core portion containing one or more selected from zirconium nitride and zirconium oxynitride; and a metal oxide coating layer formed by a metal oxide coating the core portion (refer to the results of Examples 13 and 14, etc.).
[0729] From the viewpoint of further improving the effects of the present invention, it is preferred that the alkali-soluble resin be confirmed to have an ethylenically unsaturated group such as a curable group ((meth))acryloyl group) (see comparison between Examples 2 and 19, etc.).
[0730] The same results can be obtained even when zirconium nitride is used instead of zirconium oxynitride. The same results can be obtained even when no surfactant is added. The same results can be obtained even when no polymerization inhibitor is added. The same results can be obtained even when polymerization initiators I-1 and I-2 are used in combination.
[0731] <<Test Y>>
[0732] [Application in various purposes]
[0733] The applicability of the compositions of Examples used in the above-mentioned <<Test X>> to various applications was confirmed by the following method.
[0734] [Fabrication and evaluation of light-shielding films for wafer-level lenses]
[0735] The lens film was formed by the following operation.
[0736] 1. Formation of thermosetting cured film
[0737] A curable composition for a lens (a composition obtained by adding 1% by mass of an aryl sulfonium salt derivative (SP-172 manufactured by ADEKA CORPORATION) to an alicyclic epoxy resin (EHPE-3150 manufactured by Daicel Corporation) (2 mL) was applied on a 5×5 cm glass substrate (1 mm thick, manufactured by SCHOTT, BK7), and the coating was heated at 200°C for 1 minute and cured to form a film that could be used to evaluate the residue on the lens.
[0738] 2. Evaluation on the lens
[0739] The composition of the example used in the above-mentioned <<Test X>> was applied to the glass substrate (support) on which the above-mentioned lens film was formed, and the support coated with the composition was heated for 120 seconds by a hot plate with a surface temperature of 120° C. In this way, a coating film (composition layer) with a film thickness of 2.0 μm was obtained.
[0740] <Exposure Step>
[0741] Then, a high pressure mercury lamp was used to expose the film at an exposure amount of 500 mJ / cm through a photomask having a hole pattern of 10 mm. 2 The obtained composition layer was exposed to light.
[0742] <Development Step>
[0743] The exposed composition layer was subjected to spin immersion development for 60 seconds at 23° C. using a 0.3% aqueous solution of tetramethylammonium hydroxide. Thereafter, the developed composition layer was rinsed by spin spraying, and the rinsed composition layer was further washed with pure water, thereby obtaining a patterned light-shielding film (cured film).
[0744] 〔Fabrication and evaluation of solid-state imaging devices〕
[0745] A curable resin layer was formed on a substrate having a light-shielding film in the pattern prepared above using a curable composition for a lens (a composition obtained by adding 1% by mass of an arylsulfonium salt derivative (SP-172 manufactured by ADEKA CORPORATION) to an alicyclic epoxy resin (EHPE-3150 manufactured by Daicel Corporation) and the shape was transferred using a quartz mold having a lens shape and irradiated with a high-pressure mercury lamp at 400 mJ / cm 2 The lens is cured by an exposure amount of , thereby producing a wafer-level lens array having a plurality of wafer-level lenses.
[0746] The manufactured wafer-level lens array is cut and lens modules are manufactured using the obtained wafer-level lenses. Then, an imaging element and a sensor substrate are mounted to manufacture an imaging unit.
[0747] The obtained wafer-level lens has no residue at the lens opening and has good transmittance, and also has high uniformity and high light-shielding property on the coating surface of the light-shielding layer.
[0748] [Manufacturing of color filter with black matrix]
[0749] <Formation of Black Matrix>
[0750] The composition of the example used in the above-mentioned <<Test X>> was applied to a glass wafer by spin coating, and then the glass wafer was heated on a hot plate at 120° C. for 2 minutes to obtain a coating film (composition layer). The rotation speed based on spin coating was adjusted so that the film thickness of the coating film was 2.0 μm.
[0751] Then, an i-ray stepper was used to irradiate the sample at 500 mJ / cm through a photomask having an island pattern of 0.1 mm. 2 The obtained composition layer was exposed to light at an exposure amount of .
[0752] The exposed composition layer was subjected to spin immersion development for 60 seconds at 23° C. using a 0.3% aqueous solution of tetramethylammonium hydroxide. Thereafter, the developed composition layer was rinsed by spin spraying, and the rinsed composition layer was further washed with pure water, thereby obtaining a patterned light-shielding film (black matrix).
[0753] <Preparation of Color Curable Composition>
[0754] In the composition of Example 1 in the above <<Test X>>, except that Z-1 in the dispersion 1 was replaced with the following color pigment, a colored curable composition R-1 for red (R), a colored curable composition G-1 for green (G), and a colored curable composition B-1 for blue (B) were prepared in the same manner.
[0755] ·Color pigments for forming RGB color pixels
[0756] ··Red (R) pigment
[0757] CI Pigment Red 254
[0758] ··Green (G) pigment
[0759] A 30 / 70 (mass ratio) mixture of CI Pigment Green 36 and CI Pigment Yellow 219
[0760] ··Blue (B) pigment
[0761] A 30 / 70 mixture of CI Pigment Blue 15:6 and CI Pigment Violet 23 (mass ratio)
[0762] <Production of Color Filter>
[0763] The same method as the method for preparing the black matrix prepared above was used, and a 80×80 μm red (R) coloring pattern was formed in the black matrix prepared above using the red (R) colored curable composition R-1. Furthermore, in the same manner, a green (G) coloring pattern was formed using the green (G) colored curable composition G-1, and a blue (B) coloring pattern was formed using the blue (B) colored curable composition B-1, thereby preparing a color filter having a black matrix for a liquid crystal display device.
[0764] It was confirmed that the composition of the present invention can also be suitably used for a black matrix for color filters.
[0765] Explanation of symbols
[0766] 10-headlight unit, 12-light source, 14-light shielding portion, 16-lens, 20-base, 22-light shielding film, 23-opening portion, 30-light distribution pattern, 30a-edge, 31-region, 32-light distribution pattern, 32a-edge, 33-notch portion, 34-region, 100-solid-state imaging device, 101-solid-state imaging element, 102-imaging portion, 103-cover glass, 104-spacer, 105-laminated substrate, 106-wafer substrate, 107-circuit substrate, 108-electrode pad, 109-external connection terminal, 110-through electrode, 111-lens layer, 112-lens material, 113-support body, 114, 115-light shielding film, 201- Photosensitive element, 202-color filter, 203-microlens, 204-substrate, 205b-blue pixel, 205r-red pixel, 205g-green pixel, 205bm-black matrix, 206-p hole layer, 207-readout gate part, 208-vertical transfer path, 209-element separation area, 210-gate insulating film, 211-vertical transfer electrode, 212-light shielding film, 213, 214-insulating film, 215-planarization film, 300-infrared sensor, 310-solid-state imaging element, 311-infrared absorption filter, 312-color filter, 313-infrared transmission filter, 314-resin film, 315-microlens, 316-planarization film.
Claims
1. A photosensitive composition comprising: Zirconium nitride particles containing one or more selected from zirconium nitride and zirconium oxynitride; Resin; polymerizable compounds; and Photopolymerization initiator, The zirconium nitride-based particles contain Fe atoms and Cl atoms. The zirconium nitride-based particles contain 0.001 mass % to 0.400 mass % of Fe atoms and 0.001 mass % to 0.500 mass % of Cl atoms relative to the total mass of the zirconium nitride-based particles. In the zirconium nitride-based particles, a mass ratio of the content of the Fe atoms to the content of the Cl atoms is 0.007 to 3.
000.
2. The photosensitive composition according to claim 1, wherein The zirconium nitride-based particles contain 0.010 mass % to 0.150 mass % of the Fe atoms relative to the total mass of the zirconium nitride-based particles.
3. The photosensitive composition according to claim 1, wherein The content of the Cl atoms is 0.001 mass % to 0.300 mass % based on the total mass of the zirconium nitride-based particles.
4. The photosensitive composition according to claim 1, wherein In the zirconium nitride-based particles, a mass ratio of the content of the Fe atoms to the content of the Cl atoms is 0.008 to 1.
5.
5. The photosensitive composition according to claim 1 or 2, wherein The zirconium nitride-based particles include: a core portion including one or more selected from zirconium nitride and zirconium oxynitride; and a metal oxide coating layer that covers the core portion and is formed of a metal oxide.
6. The photosensitive composition according to claim 5, wherein The metal oxide contains silicon dioxide or aluminum oxide.
7. The photosensitive composition according to claim 5, wherein The content of the metal oxide coating layer is 3% by mass to 7% by mass based on the total mass of the zirconium nitride-based particles. 8 . The photosensitive composition according to claim 1 , further comprising a black pigment. 9 . A cured film formed using the photosensitive composition according to claim 1 . 10 . A light-shielding film, which is the cured film according to claim 9 . 11 . A color filter comprising the cured film according to claim 9 . 12 . An optical element comprising the cured film according to claim 9 . 13 . A solid-state imaging element comprising the cured film according to claim 9 . 14 . An infrared sensor comprising the cured film according to claim 9 .
15. A headlight unit for a vehicle, the headlight unit comprising: light source; and a light shielding portion that shields at least a portion of the light emitted from the light source, The light-shielding portion includes the cured film according to claim 9.
Citation Information
Patent Citations
Perylene-3, 4, 9, 10-tetracarboxylic diimide dye
JP1987001753A
Novel perylene-3,4,9,10-tetracarboxylic acid diimide and use
JP1988026784B2
Manufacture of ceramic material including lead
JP1989030104A
Trap device for liquid discharge
JP1989070109A
Color mosaic filter
JP1989090403A